Characterization and Expression Analysis of KCS Genes in Cotton: Insights Into Temperature-Regulated Fuzz Development - Yuchen Song; Langjing Hua; Yanan Xu; Yuefen Cao; Xin Hu; Yurong Jiang; Junkang Rong (Plant Molecular Biology Reporter, 2026)

Knockdown of SOX4 attenuates sepsis myocardial injury by inhibiting the EZH2/H3K27me3/SOCS3 axis - Hongyan Zhao; Weirong Tao; Rong Huang; Jing Cao; Chao Xu (Mammalian Genome, 2026)

Surface texture of laser-fabricated helical microgrooves on pressure swirl nozzles for enhanced atomization characteristics - Shenghan Cao; Jianxin Deng; Shiyao Rong; Yichen Bao; Junyan Wang; Zhihui Zhang (Crop Protection, 2026)

Investigating the mechanisms of liver injury in zebrafish induced by polystyrene microplastics and 17α-methyltestosterone based on the gut-liver axis - Weiya Rong; Zijun Xiong; Chang Hu; Haiyan Zhao; Lu Cao; Jiaoxin Xie; Weiwei Wang; Jing Song; Xianzong Wang; Yu Liu; Shaozhen Liu (Environmental Pollution, 2026)

Flexural behavior and crack resistance of joints in hot-rolled section steel-UHPC composite deck under negative bending: Experiments and analysis - Wenyong Cai; Xudong Shao; Junhui Cao; Yang Wen; Rong Chen; Taowei Wang; Lin Peng; Lei Yu (Engineering Structures, 2026)

AIE-active dual-pore covalent organic framework for colorimetric/fluorescence detection and degradation of perfluorooctanoic acid - Tianyuan Yu; Shuai Liu; Shaoxi He; Guoyi Pu; Xi Zhang; Yanxiong Liu; Wenyu He; Ziyu Bao; Zezhou Zhao; Jiahui Liu; Fei Li; Rong Sheng Li; et al. (Chemical Engineering Journal, 2026)

Unraveling the short- and long-term effects of lignocellulosic pretreatment derivatives on the anaerobic co-digestion of corn straw and food waste: Digester performance, microbial community, and metabolic mechanisms - Sifan Cao; Yong-Chen Han; Xiaochang C. Wang; Rong Chen; Bao-Shan Xing (Bioresource Technology, 2026)

GF7S: A large-scale GaoFen-7 stereo dataset and self-supervised adaptation of FoundationStereo for high-resolution DSM generation - Yinxia Cao; Fenzhen Su; Dongjie Fu; Wenzhou Wu; Fengqin Yan; Rong Fan; Hao Chen; Xin Huang (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

TF2A ameliorates lipid metabolism in high fat diet mice as an oxidative derivative of EGCG with altered gut microbiota and hepatic transcriptomic profiles - Yiyun Zhang; Zongzhen Guo; Kefan Wei; Rong Li; Jiaqian Cao; Liang Zhao; Sujing Wu; Caili Feng; Qiliu Jiang; Yong Xue (Food Bioscience, 2026)

Biphasic multiplex PCR based on bead array for high-throughput and sensitive authentication of meat products - Lingfeng Yan; Rong Cao; Jiajin Wei; Hehui Long; Liming Zhang; Zhuoxuan Lu (Food Control, 2026)

Ecological restoration of coastal wetlands shapes soil carbon pools and microbial carbon cycling functions in Bohai Bay, China - Mengtuo Wen; Qiulan Zhang; Yasong Li; Jing Rong; Shengwei Cao; Yaci Liu (Estuarine, Coastal and Shelf Science, 2026)

Exposure to environmentally relevant concentrations of zearalenone disrupts blood-testis barrier via inositol-requiring enzyme 1α-dependent GA binding protein transcription factor α mRNA decay - Chen Chen; Yutong Ren; Rong Wang; Jieru Liu; Kexin Liu; Ying Cao; Shuai Lin; Bolin Liu; Yuanhua Chen (Chemico-Biological Interactions, 2026)

Differential effects of alcohol-derived serum metabolites and direct ethanol exposure on mouse preantral follicle development - Meng-Ting Cao; Yang Shi; Chun Li; Yi-Lin Fan; Zhu-Rong Hu; Le-Ning Dang; Xue-Rui He; Wei-Qiang Luo; Jing-Jing Li; Xing-Rong Yan (Chemico-Biological Interactions, 2026)

Additives-induced alteration of PVC pyrolysis pathways and emission profiles - Siying Ran; Haoran Yu; Rong Cao; Ningbo Geng; Yuan Gao; Haijun Zhang; Lidong Wu; Jiping Chen (Journal of Hazardous Materials, 2026)

Potential of RNAi targeting β-N-acetylglucosaminidase(NAG1)for controlling Dendroctonus valens LeConte (Coleoptera: Scolytidae) - Yue Sun; Qin Cao; Yong-Hao Nan; Yang-Nan Hou; Chun-Fang Qi; Ji-Gang Li; Jian-Rong Wei (Journal of Asia-Pacific Entomology, 2026)

Corrigendum to “Comprehensive metabolomics and flavoromics analysis reveal the changes in muscle flavor quality of turbot (Scophthalmus maximus) during low-temperature waterless live transport” [Food Res. Int. 240 (2026) 119625] - Shanyu Wang; Yaxin Sun; Guohui Sun; Qi Liu; Yong Xue; Rong Cao (Food Research International, 2026)

Comprehensive metabolomics and flavoromics analysis reveal the changes in muscle flavor quality of turbot (Scophthalmus maximus) during low-temperature waterless live transport - Shanyu Wang; Yaxin Sun; Guohui Sun; Qi Liu; Yong Xue; Rong Cao (Food Research International, 2026)

Ni/Cu co-doped modified Bi2WO6 microsphere for enhanced photocatalytic reduction of CO2 toward CO - Xiaolong Cai; Baiquan Jing; Rong Li; Baowei Cao; Jinbo Cao; Yunhua Xu (Chemical Engineering Journal, 2026)

Benzoic acid inhibits peach root growth and lateral root emergence by disrupting auxin homeostasis through salicylic acid accumulation - Qing Rong Zhang; Jilin Yao; Feiyang Ji; Zhilin Sun; Bing Bai; Jun Zhao; Huchen Li; Yueping Liu; Qingqin Cao; Qing Zhang; Ting Ting Xiao (Plant Cell Reports, 2026)

Poricoic acid A administered during DSS exposure attenuates acute colitis in mice and is accompanied by barrier-associated changes and endpoint fecal microbiota shifts - Mei Wang; Kunkun Zhang; Danli Wang; Mingtao Cao; Rong Yong; Xiangqian Li; Wenyi Chen; Chengcheng Peng; Jiale Chang; Lu Fang; Feiyang Zhou; Yuyue Wan; et al. (Journal of Natural Medicines, 2026)

Indigenous beneficial microbes contribute to pathogen inhibition in Chinese yam continuously cropped soil - Huanhuan Cheng; Yifan Cao; Paidamoyo Mataranyika; Ziyi Yuan; Yan Wang; Jian Yang; Luqi Huang; Zongzhuan Shen; Qirong Shen; Rong Li (Applied Soil Ecology, 2026)

Fine mapping and candidate gene analysis of tassel glume closure1 (tgc1) gene in maize (Zea mays L.) - Ziwen Shi; Jinmiao Qin; Sheng Zhang; Yujiao Gao; Qing He; Hongyang Yi; Tingzhao Rong; Moju Cao (Theoretical and Applied Genetics, 2026)

Grassland fragmentation disproportionately reduces the functional diversity and traits of predatory beetles compared with their taxonomic diversity in arid regions of China - Haixiang Zhang; Ziyu Cao; Ying Wang; Wei Sun; Wenguang Huang; Yuzhe Wang; Liping Ban; Rong Zhang; Shuhua Wei (Biodiversity and Conservation, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Mitigating bioaerosol exposure risks in high-traffic clinics: Experimental and numerical optimization of air purifier interventions - Yongxin Wang; Zhijian Liu; Lei Jiang; Zirun Shi; Zijian Li; Jingwei Liu; Rui Rong; Shiyue Li; Wentao Wu; Guoqing Cao (Journal of Hazardous Materials, 2026)

Application of optimized hydrothermal, ozone and superalkali pretreatment techniques for qualitative biogas production from corn straw: A comparative assessment - Sifan Cao; Yong-Chen Han; Huqe Farhana; Xiaochang C. Wang; Rong Chen; Yu-You Li; Bao-Shan Xing (Fuel, 2026)

Interfacial engineering of core-shell Cu@Zn nanoclusters enables methane selective CO2 electroreduction via accelerated water dissociation - Wenlong Cao; Caiyu Chen; Hai Liu; Lei Yang; Tianlong Tan; Ruiyang Xu; Chengjian Ma; Tianyu Wang; Daniel Hedman; Shigeo Maruyama; Rong Xiang; Jue Wang; et al. (Chemical Engineering Journal, 2026)

Functional characterization of the MdMYB73L gene in drought and salt stress tolerance in apple - Xiao-Wen Li; Han-Yu Dong; Ya-Qi Liu; Jing-Yi Su; Xue Wang; Chang Li; Qi-Fei Wu; Wen-Xian Zhang; Xin-Rong Shi; Hong-Jian Cao; Qiangbo Liu; Xiao-Fei Wang; et al. (Plant Molecular Biology, 2026)

Synchronized organogenesis and fragment-specific behavioral recovery in Stichopus chloronotus inform artificial asexual culture and resource restoration of fissiparous sea cucumbers - Xinxin Huang; Xiang Hu; Mengjiao Liu; Ke Chen; Rong Cao; Fei Gao; Qiang Xu (Marine Biology, 2026)

Serum exosomes protect heat-stressed mouse 2-cell embryos: Enhanced antioxidant defense and base excision repair of oxidative DNA damage - Hong-Chuan Zhang; Si-Jing Qu; Xin-Lei Yan; Rui-Cong Wang; Shi-Yong Zhu; Rong-Feng Cao; Kai-Qiang Fu; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

Exposure to high ambient temperature during pre-implantation impairs embryo transport and development in the oviduct: Potential association with ANO1 downregulation - Hong-Chuan Zhang; Rui-Cong Wang; Shi-Yong Zhu; En-Yan Wang; Yu-Feng Huang; Rong-Feng Cao; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

Chemical speciation and structure of lithium (Li) in coal gasification fine slag: Evolution mechanisms and implications for Li recovery - Biao Fu; Xia Wu; Chengxiang Yu; Xinru Zhou; Hongyan Nan; Yijun Cao; Yukun Huang; Yuhang Gao; Guangqing Hu; Zhongjie Shen; Lingkun Rong (Fuel, 2026)

Antioxidant peptides from porcine blood meal: Mechanisms of interaction with hemin via spectroscopy and molecular docking - Rong Jia; Juanjuan Du; Jinxuan Cao; Jinpeng Wang; Yuemei Zhang; Wendi Teng; Ying Wang (Food Chemistry, 2026)

Bio-inspired functionalization of PA1012 into piezoelectric ionomers via molecular asymmetry and ion-cluster polarization - Guangmou Cao; Rong Li; Qi Liang; Jingwen Liu; Pengyuan Luo; Haomeng Ma; Yang Yu; Linyi Cui; Le Xu; Jingjing Ma; Tong Lin; Liuchun Zheng (Chemical Engineering Journal, 2026)

Evaluation of the aerosol transmission patterns and the airflow organization effectiveness in the respiratory outpatient clinic - Yongxin Wang; Lei Jiang; Zhijian Liu; Duo Cai; Jingwei Liu; Rui Rong; Shiyue Li; Wentao Wu; Guoqing Cao (Building and Environment, 2026)

Cloning and functional analysis of MdCRCT1 in the regulation of drought tolerance in apple - Xiao-Wen Li; Ya-Qi Liu; Jing-Yi Su; Xin-Rong Shi; Chang Li; Xue Wang; Qi-Fei Wu; Xuan He; Hong-Jian Cao; Xiao-Fei Wang; Ting-Ting Zhang (Physiology and Molecular Biology of Plants, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Profiling hydrophobic organic pollutants in serum from vulnerable populations in Dalian, China - Yubing Dai; Ningbo Geng; Dongying Zheng; Jing Jin; Xianbo Lu; Rong Cao; Haijun Zhang; Jiping Chen (Environmental Pollution, 2026)

Temperature sensitivity and rainfall heat flux drive rapid mass loss of low-latitude glaciers in the Southeastern Qinghai–Tibet Plateau - Yanjun Che; Shijin Wang; Yun Cao; Weiwei Lv; Xinggang Ma; Congzheng Han; Jian Zhong; Rong Wu (CATENA, 2026)

AI-decoded enzymatic blueprints navigate the unknown metabolome - Shu-Xin Cao; Xiang Luo; Yu Bai; Hong-Li Tan; Rong-Rong He (Science China Life Sciences, 2026)

Imbalanced Si:N Alters Lipid Production and Photosynthesis in the Marine Diatom Phaeodactylum tricornutum and Dinoflagellate Prorocentrum donghaiense - Jiaxuan Cui; Chuanli Zhang; Rong Bi; Yunyun Zhuang; Xiaoqian Pan; Xiao Qin; Zhong Cao; Hailong Zhang; Li Li; Yang Ding; Meixun Zhao (Journal of Ocean University of China, 2026)

Unraveling the phototransformation of 2,4,6-tribromophenol: Aqueous mechanisms involving ·OH and the emergence of hydroxylated PBDEs - Junling Ma; Muhammad Zeshan; Rong Cao; Hong-bin Xie; Ningbo Geng; Haijun Zhang; Yuan Gao; Lidong Wu; Jiping Chen (Water Research, 2026)

A multicomponent Fc-fused subunit vaccine induces cross-protective immunity against porcine reproductive and respiratory syndrome virus QYYZ-like and NADC30-like strains - Linxing Tian; Zhengdan Lin; Mengxi Pan; Yanwen Wen; Mingxing Lu; Shudan Liu; Chao Zhang; Zhenxiang Rong; Jiahui Ma; Ruiqu Zhou; Nan Cao; Xinghua Chen; et al. (Veterinary Microbiology, 2026)

A germline-specific vesicular structure licenses mRNA activation during spermiogenesis and is hijacked in gastric cancer - Mingxi Liu; Zerui Wang; Yinuo Li; Qingsong Xie; Zhuang Xiao; Xuezhi He; Guanxiong Wang; Yang Gao; Yini Zhang; Lin Zheng; Xun Xia; Lujie Chen; et al. (Science Bulletin, 2026)

Valorization of catalytically improved combustion stability for low-concentration methane in a gradient pore-density porous media burner - Yunqi Cao; Haonan Rong; Li Yang; Yifan Ding; Fang Liu; Cheng Zhai (Fuel, 2026)

Dynamic alterations and crucial transitions in the flavor profile of turbot (Scophthalmus maximus) during low-temperature waterless preservation - Shanyu Wang; Ling Zhao; Huihui Sun; Qi Liu; Yaxin Sun; Guohui Sun; Yong Sun; Mingchao Pan; Yong Xue; Rong Cao (Food Research International, 2026)

Molecular epidemiology reveals co-circulation of five Anaplasma species with zoonotic potential in sheep and goats from Henan province, China - Jia-Run Yang; Wei-Hao Tan; Jie-Yue Liang; Jing-Rong Li; Yu-Ru Cao; Wan-Yu Li; Jian-Wei Shao (Comparative Immunology, Microbiology and Infectious Diseases, 2026)

Photoelectron-driven modulation of carbon metabolism enhances hydrogen production in a ZnIn2S4-Shewanella oneidensis biohybrid system - Xue-Meng Wang; Hao-Yu Li; Kai-Li Wang; Zhi-Xuan Zhang; Yu-Xin Cao; Ya-Lian Ma; Rong Chen (Bioresource Technology, 2026)

Manure addition improves soil quality in subalpine meadows by affecting fungal diversity and network complexity - Xiayan Zhou; Rong Dai; Suxing Liu; Zhengwen Wang; Yajun Bai; Wenxia Cao (Plant and Soil, 2026)

Shake table experimental study on a small radius curved bridge with unequal height piers - Chiyu Jiao; Shiqi Cao; Suiwen Wu; Yangjie Li; Rong Fang; Kangshun Wang (Soil Dynamics and Earthquake Engineering, 2026)

Unexpectedly high PCDD/F loadings on coarse particle in municipal solid waste incineration flue gas - Rong Cao; Yichi Zhang; Ningbo Geng; Haijun Zhang; Jiping Chen (Journal of Hazardous Materials, 2026)

Development of a high-throughput sensitive SB-PCR assay for rapid detection of laboratory-escaped antibiotic resistance genes - Lingfeng Yan; Shengnan Liu; Rong Cao; Azadeh Nilghaz; Jiajin Wei; Hehui Long; Liming Zhang; Zhuoxuan Lu (Journal of Environmental Chemical Engineering, 2026)

Research progress on the structure of edible fungi polysaccharides and their anti-obesity mechanisms via the regulation of intestinal microbiota and metabolites - Xin Wei; Weiya Rong; Liyang Jin; Limin Zhang; Daoqin Ren; Yue Jiang; Jinling Cao; Shaojun Yun; Feier Cheng; Wenfei Zhao; Yong Li; Mingchang Chang; et al. (Food Bioscience, 2026)

Functional division of labor within defined yeast consortia drives flavor formation during early solid-state fermentation of sichuan shai vinegar - Jiajie Zhu; Yuting Liao; Yulin Zhao; Jun Liu; Zhicheng Li; Xiangpeng Kong; Suyi Zhang; Chuan Song; Qixu Fu; Xianbin Wang; Ruiqi Xue; Xuemei Shi; et al. (Food Microbiology, 2026)

Synergistic effects of polystyrene microplastics and 17α-methyltestosterone on immune and oxidative stress responses in the gill and liver of Gobiocypris rarus - Yibo Jia; Lu Cao; Tongyao Li; Haiyan Zhao; Gen Chen; Zijun Xiong; Weiya Rong; Qing Liu; Weiwei Wang; Jing Song; Xianzong Wang; Yu Liu; et al. (Fish & Shellfish Immunology, 2026)

Multi-objective optimization of rice production and environmental sustainability under climate change in the Yangtze River Delta: A DNDC-random forest framework approach - Shuoshuo Liang; Ping He; Qingnan Chu; Wentian He; Ruochen Li; Xinpeng Xu; Rong Jiang; Shuang Liu; Linkui Cao; Zhimin Sha (Field Crops Research, 2026)

Settling and dewatering characteristics of super absorbent polymer treated fine-grained dredged sediment waste - Yupeng Cao; Jie Yin; Xinzhuang Cui; Zhehao Qiu; Shuai Zhang; Rong Wang (Journal of Soils and Sediments, 2026)

Metallogenic Age of the Qianjiadian Uranium Deposit—Evidence from Fluid Inclusions and (U-Th)/He - Ruxin Ding; Yangshijia Li; Zilong Li; Rongli Huang; Minqiang Cao; Xingzhou Chen; Hui Rong; Heping Zou (Journal of Earth Science, 2026)

A novel deep neural network with geographical position constraints for shallow water depth estimation - Xinle Guo; Rong Huang; Yusheng Xu; Bin Cao; Kuifeng Luan; Zhen Ye; Huan Xie; Xiaohua Tong (Marine Geodesy, 2026)

Rotavirus induces mucosal B-cell responses through the TLR3/TRIF and MAVS pathways - Rong-Rong Zhang; Yong-Yi Yang; Man Wang; Wen-Ru Yang; Riaz Muhammad Azeem; Fu-Xuan Niu; Ya-Xin Yang; Man-Jie Hu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Jian-Zhong Wang; et al. (Veterinary Microbiology, 2026)

SVA virus-like vesicle vaccine based on VEEV-VSVG vector elicits efficient immune responses and protection in swine - Zhenxiang Rong; Mingjin Jiao; Nan Cao; Mingxing Lu; Shudan Liu; Chao Zhang; Liuqing Wei; Yamei Li; Huanchun Chen; Xiangmin Li; Ping Qian (Veterinary Microbiology, 2026)

Coordination-tailored conductive metal-organic frameworks boost CO2 electroreduction to ethylene for cascade ethylene glycol production - Hui Guo; Shao-Shuai Zhao; Duan-Hui Si; Weijin Li; Zi-Ao Chen; Rong Cao; Roland A. Fischer; Yuan-Biao Huang (Science Bulletin, 2026)

Gut microbiome succession and cultivation-based functional screening during intestinal regeneration in Stichopus monotuberculatus - Xinyuan Yang; Rong Cao; Chenghao Jia; Fei Gao; Qiang Xu (Marine Environmental Research, 2026)

Identifying the genesis and evolution of geothermal water in the coal mining area, North China: Insights from hydrochemistry and δ2H, δ18O, δ13C, δ34S and 87Sr/86Sr isotopes - Jie Zhang; Herong Gui; Luwang Chen; Manli Lin; Huifang Rong; Jun Li; Ruirui Li; Mingda Cao (Geothermics, 2026)

Effect of structural characteristics of highland barley β-glucan by various thermal processing methods on intestinal microbial community and fermentative products - Rong Li; Ji Gao; Yiyun Zhang; Zijian Dai; Siqi Li; Tong Wu; Jiaqian Cao; Kefan Wei; Chao Wang; Qun Shen; Yong Xue (Food Bioscience, 2026)

Response of source capacity to elevated ozone during grain filling determines ozone sensitivity of wheat cultivars - Yanze Ma; Yansen Xu; Xintong Hu; Evgenios Agathokleous; Kazuhiko Kobayashi; Xinyou Yin; Rong Cao; Zhaozhong Feng (Field Crops Research, 2026)

Jinxinkang Granule Preserves Myocardial Function by Suppressing Cardiac Senescence Through the cGAS-STING Axis in a Pressure Overload Mouse Model of Heart Failure - Jingping Sun; Kang Xie; Yingxie Cao; Liang Kang; Rong Li (Cardiovascular Toxicology, 2026)

Recyclable Na-Mn-O nanocomposite for dual-modal photothermal/ROS antibacterial therapy against multidrug-resistant bacteria in pathogen-laden wastewater - Zhi-ru Tao; Shu-xian Hou; Yi-mei Wang; Xue-chao Shi; Xin-xin Liu; Jun Ge; Yu-han Ji; Ya-qi Cheng; Zi-yi Leng; Xin-yv Cao; Rong-rong Li; Jin-nan Xuan; et al. (Journal of Water Process Engineering, 2026)

Occurrence and prioritization of hydrophobic pollutants in China’s coastal marine biota - Haichao Mu; Ye Sun; Xiaodan Pei; Xuchun Li; Jiajia Wu; Wenwen Wang; Rong Cao; Xing Liu; Ziwei Yao (Journal of Hazardous Materials, 2026)

Enhancement towards fast gas heating in non-equilibrium plasma assisted ammonia ignition - Yong Hu; Zhencao Zheng; Ruijiao Cao; Weixin Rong; Feiyang Zhao; Wenbin Yu (Fuel, 2026)

Assessment and remediation model of eco-geo-environmental conditions in arid limestone mining areas - Siyuan Cao; Ying Yuan; Wensong Zhang; Miao Zhang; Aihong Zhou; Ningbo Han; Miren Rong (Ecological Engineering, 2026)

Modulation of oligomerization profiles in chitosan degradation by key chitosanase residues via steric and hydrophilic effects - Minjuan Gui; Yingying Wei; Huihui Sun; Ling Zhao; Xiangzhao Mao; Rong Cao (Carbohydrate Polymers, 2026)

Glycine Drives IMP Production in Hybrid Bream (Megalobrama Amblycephala ♀ × Culter Alburnus ♂) Via Concerted Action: Activating glycyl-tRNA Synthetase and Fueling the Pentose Phosphate Pathway - Zhehua Xu; Weiting Zhang; Ruijie Zhan; Jiefan Zhou; Man Chen; Yonghua Zhou; Fufa Qu; Rong Zhou; Shaochun Liu; Shenping Cao; Jianzhou Tang; Zhen Liu (Marine Biotechnology, 2026)

Corrigendum to “Carbon sink potential and planning and governance strategies of ecological space in megacities: A case study of Beijing” [Sustainable Cities and Society 136 (2026) 12/107036] - Qiwen Cao; Aman Zhang; Rong Cong; Dan Zhao; Xiaochun Huang; Shanshan Ning; Xiaoran Xie (Sustainable Cities and Society, 2026)

Carbon sink potential and planning and governance strategies of ecological space in megacities: A case study of Beijing - Qiwen Cao; Aman Zhang; Rong Cong; Dan Zhao; Xiaochun Huang; Shanshan Ning; Xiaoran Xie (Sustainable Cities and Society, 2026)

Field-free topological spin textures enable spin selectivity for spin light-emitting diodes - Yongping Wei; Shuo Cao; Chenhao Zhang; Xinran Wang; Sihao Ren; Hongshu Li; Yi Yang; Jiangpeng Zhou; Mingyu Chen; Shiming Wu; Weisheng Zhao; Xichao Zhang; et al. (Science Bulletin, 2026)

Effects of mineral inputs on organic phosphorus (Adenosine 5′-monophosphate) sorption and implications for its biogeochemical behavior on marine sediments - Yu Meng; Meng Lv; Xiao-Tong Zhang; Xiao-Yan Cao; Rong Chen; Gui-Peng Yang (Marine Chemistry, 2026)

Cerium isotopic compositions of deep-sea sediments: implications for geochemical behavior of rare earth elements in the pelagic seafloor - Ganglan Zhang; Jianghao Bai; Mingyu Zhao; Pengcong Wang; Yangtao Zhu; Jun Cao; Hao Wu; Rong Xu; Gaowen He; Gangjian Wei; Yinan Deng (Geochimica et Cosmochimica Acta, 2026)

Fast predictions of plasma-assisted NH3/air combustion based on model downscaling and machine learning coupled with kinetics mechanism - Ruijiao Cao; Hongge Kang; Yong Hu; Zhencao Zheng; Weixin Rong; Feiyang Zhao; Wenbin Yu (Fuel, 2026)

Green Intelligent Fertilizer derived from yellow phosphorus slag boosts rice yield and mitigate environmental impacts in high-altitude watersheds - Suoqian Kang; Ou Yu; Shuntao Zhang; Yujiao Tan; Rui Wang; Xueli Du; Jun Cao; Zhong Duan; Fei Huang; Rong Li; Changzhou Wei; Jiujiang Xu (Field Crops Research, 2026)

Formation mechanism of localized corrosion area for pre-oxidized high-silicon ferritic/martensitic steel immersing in the oxygen-saturated liquid lead–bismuth eutectic (LBE) - Xinyu Cao; Junhua You; Yangpeng Zhang; Lijian Rong; Desheng Yan (Annals of Nuclear Energy, 2026)

A novel multiplex RPA/CRISPR-Cas12a integrated biosensor for on-site detection of high-risk HPV genotypes - Yuying Bao; Wei Ding; Ling Zhang; Wei Wang; Jia Liu; Yiting Qu; Liguo Zhu; Kairui Zhang; Guanxi Zhong; Rong Han; Qiang Shen; Bo Wang; et al. (Analytica Chimica Acta, 2026)

Rare earth element hyperaccumulation in vascular plants: Occurrence, mechanisms, and applications - Ruo-Rong Liu; Cui-Ling Huang; Hong-Xiang Zheng; Chong Liu; Rui-Qi Zhang; Yue Cao; Antony van der Ent; Can-Die Xie; Wen-Shen Liu; Jean Louis Morel; Catherine Sirguey; Damien Blaudez; et al. (Critical Reviews in Environmental Science and Technology, 2025)

Polarization electric field tuning interface electric field in full-spectral response double S-scheme heterojunction to drive synchronous removal of Cr(VI) and RBR X-3B - Jing Bai; Xiangling Zhang; Chen Wang; Xuhao Li; Shilong Cao; Rong Zhang; Jiezhou Hu (Water Research, 2025)

Advancements in urban water management and ecological restoration technologies: Frameworks, challenges, and emerging trends - Sitong Zou; Yucong Zheng; Mawuli Dzakpasu; Qian Li; Ting Cao; Liping Zhao; Tianfu Wu; Dongfu Zhang; Yunze Chai; Rong Chen (Journal of Water Process Engineering, 2025)

Oyster-mussel differences in cadmium accumulation linked to molecular weight distribution of Cd-binding proteins - Guangbin Zhong; Xue Cao; Sen Du; Canchuan Zhang; Li Zhang; Niklas Helle; Minwei Xie; Rong Chen; Qiao-Guo Tan (Journal of Hazardous Materials, 2025)

Reversing the paradigm: Oxygen-dependent switch of nTiO₂ from promoting to suppressing ARG conjugation - Jie Yu; Xin Wang; Ya-Xin Hu; Feng-Ting Cao; Qiu-Rong Zhang; Xiang-Tong Zhou; Xiang Xiao (Journal of Hazardous Materials, 2025)

Corrigendum to “Synthesis of an autochthonous microbial community by analyzing the core microorganisms responsible for the critical flavor of bran vinegar” [Food Res. Int. 175 (2024) 113742] - Li Li; Na Li; Junjie Fu; Jun Liu; Xue Ping Wen; Hong Cao; Hongwei Xu; Ying Zhang; Rong Cao (Food Research International, 2025)

Ginkgolic acids-enriched nanoemulsions: A green strategy for broad-spectrum antimicrobial delivery - Qihui Dong; Rong Wu; Jun Cao; Fuliang Cao; Pengfei Yu; Erzheng Su (Food Chemistry, 2025)

Corrigendum to “Regulation of cell migration through cross-sectional morphology design to facilitate implant-to-ureter regeneration” [Chem. Eng. J. Volume 523 (2025) 168846] - Baiyang Song; Zonghuan Wang; Junjun Huang; Yiwei Hu; Fang Yang; Zewen Shi; Yuhao Cao; Li Fang; Hao Rong; Zejun Yan; Junhui Jiang; Ruoyu Zhang; et al. (Chemical Engineering Journal, 2025)

Unraveling the role of pyridyl sites in UiO-67 type MOFs supported Pd NPs for boosting formic acid dehydrogenation - Jiewei Rong; Rongmei Zhang; Mai Xu; Xu Chen; Xinyue Yang; Jinsong Hu; Xiru Cao; Zhentao Liu; Chunming Xu; Chunhui Zhou; Xilong Wang (Chemical Engineering Journal, 2025)

Novel compound bacterial agent effects on pig farm wastewater denitrification and nitrogen transformation - Rong Gao; Zhuangzhuang Liu; Weikun Li; Liu Lou; Tong Xu; Lin Shi; Jie Cao; Jun Fang; Gang Liu (Bioresource Technology, 2025)

The crucial role of immune factors in susceptibility to SARS-CoV-2 infection and severity of COVID-19 - Xing-Hao Yu; Rong-Rong Cao; Yi-Qun Yang; Han-Wen Cao; Fei-Yan Deng; Shu-Feng Lei (Molecular Genetics and Genomics, 2025)

Utilization of river and lake dredged sediments for growing medium Preparation and its effect on the growth of alfalfa and bermudagrass: Germination, growth, and feasibility analysis - Rong Zhang; Xiangling Zhang; Bi Wu; Chen Wang; Jing Bai; Xuhao Li; Lingwei Kong; Zhouying Xu; Shilong Cao; Xinlu Xiao (Journal of Soils and Sediments, 2025)

IFNGR1, IRF8 genetic polymorphisms modulate the susceptibility of non-tuberculous mycobacteria pulmonary disease and influence the patients’ treatment outcomes and immune status - Li-ping Cheng; Zhi-bin Liu; Lei Wang; Jie Cao; Qing-rong Qu; Hai Lou; Xiao-na Shen; Juan Yang; Yuanyuan Yu; Rui Juan Zheng; Wei Sha; Qin Sun (Inflammation Research, 2025)

Knockout of the Agrobacterium ILVC gene generates a valine-isoleucine auxotrophic strain for plant transformation - Yanhui Yang; Jun Lu; Tianrui Xue; Zhenli Cao; Mingjie Li; Zhongyi Zhang; Rong Wang; Tongyu Wu (Transgenic Research, 2025)

Non-extractable residues as the dominant fate of bisphenol A (BPA) in oxic paddy soil: formation and characterization - Yanan Zhao; Yongfeng Wang; Xiaoran Guo; Siqi Cao; Bingqi Jiang; Yao Yao; Xiaolong Liang; Rong Ji (Science of The Total Environment, 2025)

Unveiling the gut-vascular connection: Gut microbiota regulates cardiovascular toxicity induced by combined exposure to PM2.5 and high-fat diet via butyric acid/NLRP3 pathway - Jiayu Tian; Jiaji Cheng; Huan Yang; Zeyu Niu; Lifang Zhao; Linlin Guan; Nannan Liu; Shuling Rong; Caihong Wang; Dongxing Shi; Huiqiu Zheng; Na Cao; et al. (Journal of Hazardous Materials, 2025)

Carbohydrate-metabolizing gastrointestinal bacteria mediate resistome divergence in high feed efficiency Holstein dairy calves - Tianyu Chen; Shangru Li; Jianxin Xiao; Rong Peng; Mo Sha; Jingjun Wang; Jiaying Ma; Wei Wang; Mei Ma; Shengli Li; Zhijun Cao; Shuai Liu (Journal of Hazardous Materials, 2025)

Low-dose cadmium enhances coronavirus infectivity by amplifying viral receptor and suppressing goblet cell differentiation - Yanan Cao; Liangxing Xia; Yanjie Huang; Xueli Zhang; Chunxiao Mou; Zhenhai Chen; Rong Zhou; Shuai Zhang; Wenbin Bao (Journal of Hazardous Materials, 2025)

Arginyl-fructosyl-glucose and arginyl-fructose as bioactives from red ginseng: efficient aqueous preparation and their protective effects on aging-related erectile dysfunction in rats - Jialing Cao; Rong Tsao; Cheng Yang; Yun Wang; Lianfu Zhang (Food Bioscience, 2025)

Compartment engineering in yeast: a path to increased biochemical production - Yuyang Wang; Liyan Cao; Lanxin Rong; Chen Ding; Chang Liu; Qingqing Ye; Qingeng Huang; Cui-ying Zhang; Ning Xu; Jiwei Mao; Jee Loon Foo; Aiqun Yu (Chemical Engineering Journal, 2025)

Regulation of cell migration through cross-sectional morphology design to facilitate implant-to-ureter regeneration - Baiyang Song; Zonghuan Wang; Junjun Huang; Yiwei Hu; Fang Yang; Zewen Shi; Yuhao Cao; Li Fang; Hao Rong; Zejun Yan; Junhui Jiang; Ruoyu Zhang; et al. (Chemical Engineering Journal, 2025)

The potential role of hydrogen sulfide-autophagy axis in diseases - Ti Chu; Yan-Wen Wang; Lei Cao; Xue-Li Wang; Yong-Qi Fan; Yu-Hang Chen; Yi Zhang; Wei-Rong Si; Qi-Ying Jiang; Dong-Dong Wu (Journal of Physiology and Biochemistry, 2025)

Homologous nanocellulose modification: A “like cures like” strategy against coffee-ring and infiltration effects in paper-based colorimetric detection - Linan Sun; Yafei Lou; Siyu Chen; Hongyue Weng; Jiahao Li; Zhihui Lin; Junfei Tian; Rong Cao (Analytica Chimica Acta, 2025)

Navigating the lunar frontier: one hundred landing sites at the south pole for future mission challenges - Yongjiu Feng; Pengshuo Li; Haoteng Li; Yan Liu; Mengrong Xi; Rong Wang; Shurui Chen; Panli Tang; Yuze Cao; Qian Huang; Qionghua You; Shijie Liu; et al. (Science Bulletin, 2025)

A sliding window method considering image shadow to detect Mars rock from MRO HiRISE datasets - Na Sun; Yongjiu Feng; Xiaohua Tong; Pengshuo Li; Rong Wang; Yuhao Wang; Yuze Cao; Zilong Cao; Xiong Xu; Yusheng Xu; Shijie Liu (Planetary and Space Science, 2025)

Tracing toxic pollutants in coastal urban atmosphere: A case study on the particle-size distribution, sources, and health risks of PCDD/Fs, PCBs, PAHs, and substituted PAHs - Zhangpeng Guo; Shuai Sun; Rong Cao; Nan Jiang; Naibing Liang; Zichen Wang; Jiasen Guo; Minzhen Li; Xing Liu; Ningbo Geng; Jiping Chen (Journal of Hazardous Materials, 2025)

DPP-IV inhibitory peptides from highland barley via machine learning and multi-scale validation - Xin Bao; Yiyun Zhang; Liyang Wang; Zijian Dai; Rong Li; Kefan Wei; Jiaqian Cao; Qingyu Zhao; Qun Shen; Yong Xue (Food Chemistry, 2025)

Integrated Biofilm Modification and Transcriptional Analysis for Improving Fengycin Production in Bacillus amyloliquefaciens - Chun-Yang Cao; Zheng-Jie Hou; Ming-Zhu Ding; Geng-Rong Gao; Bin Qiao; Si-Yu Wei; Jing-Sheng Cheng (Probiotics and Antimicrobial Proteins, 2025)

Network pharmacology, molecular docking, and molecular dynamics simulation analysis reveal the molecular mechanism of halociline against gastric cancer - Xiangru Zha; Rong Ji; Yang Li; Rong Cao; Songlin Zhou (Molecular Diversity, 2025)

In Situ isotope tracing for metal bioaccumulation in open waters: Implications for interpreting biomonitoring data and safe seafood aquaculture - Haiyan Xiong; Tao Wang; Xue Cao; Jing Qian; Stuart L. Simpson; Rong Chen; Qiao-Guo Tan; Minwei Xie (Journal of Hazardous Materials, 2025)

Metatranscriptomic insights into nitrogen loss mediated by multi-kingdom microbial interactions in periphytic biofilms under imidacloprid exposure - Zuqiang Cao; Juan Chen; Chao Wang; Peifang Wang; Han Gao; Bingbing Feng; Bo Zhang; Rong Wang; Ge Cui (Journal of Hazardous Materials, 2025)

Personnel exposure studies to multi-source diffusion of bioaerosols under biosafety laboratory - Level 2 plus operating conditions - Yongxin Wang; Zhijian Liu; Chuan Jiang; Lei Jiang; Jingwei Liu; Rui Rong; Shiyue Li; Wentao Wu; Guoqing Cao (Journal of Hazardous Materials, 2025)

Structural-taste relationship and molecular interaction mechanisms of umami peptides from Meretrix lyrata hydrolysates: Insights into key binding sites and thermodynamic drivers - Chunyong Song; Rong Jiang; Mingtang Tan; Zhongqin Chen; Huina Zheng; Jialong Gao; Haisheng Lin; Wenhong Cao (Food Bioscience, 2025)

Removal notice to “Assessment and remediation model of eco-geo-environmental conditions in arid limestone mining areas” [Ecological Engineering 217 (July 2025) 107644] - Siyuan Cao; Ying Yuan; Wensong Zhang; Miao Zhang; Aihong Zhou; Ningbo Han; Miren Rong (Ecological Engineering, 2025)

Study on the field-scale bacterial growth dynamics and ecological effects of microbial dust suppression - Haoran Wang; Yi He; Rong Liu; Jie Chen; Yongjiang Wen; Kunyu Yan; Yong Cao (Chemical Engineering Journal, 2025)

Pressure-adaptive core–shell liquid metal microspheres for reliable flip-chip interconnects - Jingtian Li; Yingjie Duan; Huixia Cao; Yong Wang; Xi Lu; Yadong Xu; Rong Sun; Yougen Hu (Chemical Engineering Journal, 2025)

Organic micropollutants in surface water across China: Occurrence and ecological risk - Rong Cao; Ye Sun; Shuai Sun; Xiaoli Sun; Fanyu Meng; Yueyi Xia; Yuan Gao; Ningbo Geng; Haijun Zhang; Jiping Chen (Water Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Investigation into the bromination of polybrominated dibenzo-p-dioxins and dibenzofurans - Dan Li; Rong Cao; Haijun Zhang; Yun Fan; Mingyong Zhou; Haitao Shi; Jiping Chen (Journal of Hazardous Materials, 2025)

Transcriptome analysis reveals the molecular mechanisms of the 8-day infection cycle of Ecytonucleospora hepatopenaei in Litopenaeus vannamei and the host's molecular responses - Yan Rong; Yi Qiao; Tingyue Liu; Xiaohui Cao; Ge Jiang; Jie Cheng; Huiwen Jiang; Xianping Fan; Hui Shen (Fungal Biology, 2025)

The antibacterial activity, action mechanisms and prospects of Baicalein as an antibacterial adjuvant - Liuqing Mu; Kaiyan Xie; Rong Chen; Jiang Cao; Yang Shu; Xuebin Huang (World Journal of Microbiology and Biotechnology, 2025)

Mobile Genomic Island GEI-FN1A in Aeromonas salmonicida FN1 Contributes to the Spread of Antibiotic-Resistance Genes - Xinru Xie; Zhaorui Ren; Rong Wang; Kanglu Tian; Xindi Huang; Yang Lyu; Guangxiang Cao; Jiafang Fu (Current Microbiology, 2025)

Microplastics impair wound healing via NAT10-mediated epigenetic dysregulation of FASN-PI3K/AKT signaling - Feng-Jie Shen; Wei-Nan Cao; Xue-Chun Han; Qiu-Yue Pan; Yuan Wang; Rong Zhang; Gang Wei; Jin-Kui Yang (NanoImpact, 2025)

Conceptualization and assessment of groundwater–seawater interactions on bedrock islands - Rong Gong; Dongmei Han; Yi Xiao; Xianfang Song; Wei Wang; Yanling Cao (Journal of Hydrology, 2025)

LoGAN: A novel local attentive generative adversarial resizable network for detailed 3D reconstruction of the Martian surface using monocular HiRISE images and DTMs - Jiarui Cao; Rong Huang; Yusheng Xu; Zhen Ye; Jia Qian; Ludwig Hoegner; Xiaohua Tong (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Sustainable production of phloretin using multi-dimensionally adjustable acidic deep eutectic solvents as multifunctional solvents for green and efficient valorization of Malus plant pruning waste - Rong Wu; Lu Zhang; Kehong Liang; Feng Zhu; Longxin Lai; Jun Cao; Pengfei Yu; Fuliang Cao; Erzheng Su (Food Bioscience, 2025)

Multi-omics evaluation of feeding strategies on yak meat quality: insights from eDNA, metagenomics, and metabolomics - Zhengwen Wang; Haitao Yu; Yuxin Meng; Suxing Liu; Rong Dai; Xiayan Zhou; Shangli Shi; Wenxia Cao (Food Bioscience, 2025)

Aging influence and long-term stable mechanism of biofuel ash immobilizing cadmium in alkaline soil combining artificial aging simulation - Le Song; Wengeng Cao; Yu Ren; Rong Zhang; Zhaoji Zhang; Jiazhong Qian (Environmental Research, 2025)

Independent and joint effects of volatile organic compounds on pulmonary function in U.S. adults from NHANES: the mediating role of platelet-to-lymphocyte ratio - Yan-Fei Wei; Hao-Wen Chen; Kuan Liu; Shi-Ao Wang; Wei-Dong Fan; Zhan-Hui Shao; Bi-Fei Cao; Yong-Qi Liang; Zheng-Yun Xu; Kai-Yue Liao; Zi-Xuan Zhao; Lu-Rong Yang; et al. (Environmental Pollution, 2025)

Insights into immune and oxidative stress in rural homemakers exposed to VOCs during typical solid fuel utilization activities - Rong Feng; Hongmei Xu; Liyan Liu; Jieting Zhou; Hongai Zhang; Zhenxing Shen; Mengyun Yang; Jian Sun; Steven Sai Hang Ho; Junji Cao (Environmental Pollution, 2025)

A new insight into the mechanism of cadmium-induced nephrotoxicity and antagonism of selenium nanoparticles: modulation of MTF1-MT axis dependent metal homeostasis - Yi-Xi Tang; Hui-Lin Cao; Jia-Rong Hou; Jian Chen; Shi-Yong Zhu; Yun-Shuang Liang; Zhou-Yi Yang; Kanwar Kumar Malhi; Xin-Yue Mao; Jin-Long Li (Environmental Pollution, 2025)

REMOVED: Assessment and remediation model of eco-geo-environmental conditions in arid limestone mining areas - Siyuan Cao; Ying Yuan; Wensong Zhang; Miao Zhang; Aihong Zhou; Ningbo Han; Miren Rong (Ecological Engineering, 2025)

High-efficiency and stable perovskite solar cells via bidentate chelation for facet-engineered growth of FAPbI3 (111) crystals - Song Zhang; Yucong Zhou; Zhitao Shen; Yingying Li; Jian Song; Yicong Gao; Zezhi Wang; Bohao Zhang; Chong Chen; Rong Liu; Ying Liu; Ruirui Cao; et al. (Chemical Engineering Journal, 2025)

Fine mapping and functional validation reveal two incomplete dominant genes controlling photoperiod-sensitive flowering in Gossypium hirsutum - Langjing Hua; Chao Xu; Xiao Liu; Zhicheng Wang; Tengyu Li; Yuefen Cao; Xin Hu; Yurong Jiang; Junkang Rong (Theoretical and Applied Genetics, 2025)

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

Integrated transcriptomic and metabolomic analysis reveals molecular mechanisms of infectious myonecrosis virus (IMNV) pathogenesis in Litopenaeus vannamei muscle tissue - Yan Rong; Yi Qiao; Xiaohui Cao; Ge Jiang; Jie Cheng; Huiwen Jiang; Hui Shen (Aquaculture, 2025)

Transitional chromitites within the Maqsad crust-mantle transition zone of the Semail ophiolite formed above the nascent forearc setting - Rong-Zhong Bo; Peng-Jie Cai; Dong-Yang Lian; Jing-Sui Yang; Sobhi Nasir; Hui-Chao Rui; Yu-Xiao Lu; Chu-Qi Cao; Ahmed E. Masoud (Lithos, 2025)

Size-dependent internalization of polystyrene microplastics as a key factor in macrophages and systemic toxicity - Wei-Qiang Luo; Meng-Ting Cao; Chen-Xuan Sun; Jun-Jian Wang; Meng-Xi Gao; Xue-Rui He; Le-Ning Dang; Yang-Yang Geng; Bing-Yao Li; Jing Li; Zhi-Cheng Shi; Xing-Rong Yan (Journal of Hazardous Materials, 2025)

High-moisture soy protein extrudates with different moisture contents: Texture, structure, and in vitro digestion characteristics - Yiyu Zang; Rong Yang; Shurui Wang; Cuixia Sun; Yiguo Zhao; Yiping Cao; Wei Lu; Yin Zhang; Yapeng Fang (Food Research International, 2025)

Metabolite analysis indicates role of flavones and free fatty acids in water deficit stress response of Cenchrus spinifex - Jing Cao; Zhensong Li; Thomas A. Monaco; Yuping Rong (Flora, 2025)

QTL Mapping and Candidate Gene Analysis for Wax Trait of Stem and Leaf in Durum Wheat (Triticum turgidum L. ssp. durum (Desf.)) - Yijing Cai; Yasir Muhammad; Yujie Zhou; Yuefen Cao; Junkang Rong; Xin Hu (Plant Molecular Biology Reporter, 2025)

Nrf2 Ameliorates Sevoflurane-Induced Cognitive Deficits in Aged Mice by Inhibiting Neuroinflammation in the Hippocampus - Junhua Li; Jinfeng Li; Yafang Liu; Chuwen Hu; Hui Xu; Dong Cao; Rong Zhang; Kun Zhang (Molecular Neurobiology, 2025)

Creating a novel engineered tobacco chassis with downregulated expression of β-1,2-xylosyltransferase - Rong Han; Anran Xu; Yangzhong Wang; Jing Cao; Muhammad Naeem; Weihua Zhao; Lingxia Zhao (Journal of Plant Biochemistry and Biotechnology, 2025)

Optimization strategy for Cr(VI) removal in coke-based modular constructed wetlands: A comprehensive analysis of purification efficiency, removal mechanisms, and practical feasibility - Xinlu Xiao; Xuhao Li; Xiangling Zhang; Chen Wang; Xiaoting Liu; Jing Bai; Rong Zhang; Shilong Cao; Jiezhou Hu; Zhenchao Liu; Jun Shen (Journal of Environmental Management, 2025)

Oil pollution risks on coastlines in the Eastern China Seas - Ruichen Cao; Junting Guo; Zengrui Rong; Haibo Chen; Xianqing Lv (Environmental Pollution, 2025)

Temporal dynamics and task-dependent neural mechanisms in facial symmetry processing - Jian Wang; Rong Cao; Song Xue (Experimental Brain Research, 2025)

Steering CO2 electroreduction to hydrocarbons over 2D thiol-based conductive metal-organic framework - Qiu-Jin Wu; Duan-Hui Si; Yu-Liang Dong; Qian Chen; Li-Li Han; Rong Cao; Yuan-Biao Huang (Science Bulletin, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Self-powered and self-sensing water meter using contact-separation triboelectric nanogenerator with harvesting local head loss - Da-Qi Cao; Xiao-Dan Liu; Rong-Kun Fang; Guri Yihuo; Yun-Feng Wu; Zhan-Gao Huang; Wen-Yu Zhang; Xiangyu Chen; Xiao-Di Hao (Journal of Water Process Engineering, 2025)

Comparative analysis of three extraction methods for ginger leaf polysaccharide: Chemical composition, antioxidant activity, and hypolipidemic effects - Zhong-hao Zhang; Zhong-hua Zhao; Tian-yi Cao; Cai-rong Yang; Zi-zhong Tang; Shi-ling Feng; Shu Yuan; Sheng-lin Hu; Ming Yuan (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Stacking paper sheets into multi-purpose quick response sensing code with built-in nitrocellulose-membrane-free lateral flow assay for detecting tetracycline in food samples - Rong Cao; Yafei Lou; Zhiyuan Yang; Linan Sun; Azadeh Nilghaz; Miaosi Li; Junfei Tian (Food Chemistry, 2025)

Recombinant probiotic Escherichia coli delivers the polymeric protein of swine influenza virus for protection - Jin-Mei Sun; Wen-Qiang Zhang; Yan-Jin Li; Tian-Kui Guo; Rong-Rong Zhang; Yong-Lei Yang; Ying Zhao; Ling-Jiao Yu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; et al. (Veterinary Microbiology, 2025)

Effects of different concentrations of N-acetylcysteine on the sperm quality, antioxidant enzyme activity, and antioxidant gene expression of cryopreserved goat semen - Xiaodong Wang; Jinhong Luo; Maosheng Cao; Yonghong Ju; Qingmeng Long; Rong Yang; Quan Ji; Guangbin Zhou; Junwei Zhang; Ruiyang Li; Xiang Chen (Theriogenology, 2025)

Effect of temperature on 2H/1H fractionation in semi-continuous cultures of a marine diatom, coccolithophore, and dinoflagellate - Jiawei Gao; Rong Bi; Julian P. Sachs; Hailong Zhang; Yunning Cao; Matthew D. Wolhowe; Weiguo Liu; Meixun Zhao (Geochimica et Cosmochimica Acta, 2025)

Hidden threat in turbid waters: Quantifying and modeling the bioaccumulation and risks of particulate metals to clams - Jing Qian; Xue Cao; Haiyan Xiong; Fengjie Liu; Minwei Xie; Rong Chen; Qiao-Guo Tan (Environmental Pollution, 2025)

Procyanidin B2 alleviates damage to mouse testicular tissue after freezing by inhibiting oxidative stress and apoptosis - Guorui Cao; Chunyuan Li; Jian Zhang; Liwen Deng; Rong Li; Changlong Xu (Cryobiology, 2025)

Recent advancements in cation-intercalated vanadium oxide cathode materials for zinc-ion batteries - Kunxuan Li; Rong Li; Tiantian Guan; Lei Wang; Lingling Xie; Qing Han; Xuejing Qiu; Xiaoyu Cao; Limin Zhu (Chemical Engineering Journal, 2025)

Vitamin C alleviates intestinal damage induced by 17α-methyltestosterone in Carassius auratus - Haiyan Zhao; Tongyao Li; Chenyang Li; Zijun Xiong; Weiya Rong; Lu Cao; Gen Chen; Qing Liu; Yu Liu; Xianzong Wang; Shaozhen Liu (Aquatic Toxicology, 2025)

Identification of Potential Causal Genes for Neurodegenerative Diseases by Mitochondria-Related Genome-Wide Mendelian Randomization - Kang-Fu Yin; Ting Chen; Xiao-Jing Gu; Zheng Jiang; Wei-Ming Su; Qing-Qing Duan; Xiang-Jin Wen; Bei Cao; Ju-Rong Li; Li-Yi Chi; Yong-Ping Chen (Molecular Neurobiology, 2025)

Climate change enhances greening while human activities accelerate degradation in northern China's grasslands - Feifei Cao; Leizhen Liu; Yuping Rong; Nan Jiang; Lin Zhao; Qian Zhang; Zhitao Wu; Wenhui Zhao; Sheng Li (Science of The Total Environment, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Green process for xylo-oligosaccharide production from acetic acid hydrolysis of sugarcane bagasse by an integrated membrane technology and activated carbon adsorption - Qian Li; Yan Li; Jianjian Niu; Xiaofeng Hang; Weifeng Cao; Rong Fan; Yinhua Wan (Journal of Environmental Management, 2025)

Mechanistic insights into efficient phosphorus adsorption and recovery from water using functional ZnO/ZnFe-LDHs alginate hydrogels - Shilong Cao; Xiangling Zhang; Shuqin Xie; Chen Wang; Jing Bai; Xuhao Li; Rong Zhang; Xinlu Xiao; Jiezhou Hu; Xiaoxia Jiang (Journal of Environmental Chemical Engineering, 2025)

Enhanced carrier separation and photocatalytic degradation of oxytetracycline via S-scheme MIL-53(Fe)/FeOCl heterojunction composites with peroxydisulfate activation - Wei Dong; Chunyan Du; Yin Zhang; Jiao Cao; Jingyi Jiang; Lu Zhou; Guanlong Yu; Yulv Zou; Huaiyuan Peng; Rong Yan; Yu Yang (Journal of Environmental Chemical Engineering, 2025)

Contribution of phosphorylation modification by sodium tripolyphosphate to the functional properties of hollow zein nanoparticles - Sheng-qi Rao; Cao-chen Jia; Lin Du; Wei-biao Zhou; Wen-xuan Hu; Yi Jiang; Zhi-rong Wang; Zhen-quan Yang (Food Research International, 2025)

Amadori compounds: analysis, composition in food and potential health beneficial functions - Jialing Cao; Cheng Yang; Jian Zhang; Lianfu Zhang; Rong Tsao (Critical Reviews in Food Science and Nutrition, 2025)

Relationship between physicochemical properties, non-volatile substances, and microbial diversity during the processing of dry-cured Spanish mackerel - Shanyu Wang; Chong Jian; Ling Zhao; Huihui Sun; Qi Liu; Rong Cao (Food Research International, 2025)

Characterization of a Novel Tn7-like Transposon Carrying blaDHA-1 in Providencia stuartii MF1 Isolated from Swine Wastewater - Shijie Ou; Xinyi Tian; Zhen Zhang; Lingjia Zhu; Rong Wang; Guangxiang Cao; Jiafang Fu; Peipei Zhang (Current Microbiology, 2025)

A Meta‐Analysis of Bycatch Mitigation Methods for Sea Turtles Vulnerable to Swordfish and Tuna Longline Fisheries - Hao Yan; Cheng Zhou; Eric Gilman; Jie Cao; Rong Wan; Fan Zhang; Jiangfeng Zhu; Liuxiong Xu; Liming Song; Xiaojie Dai; Siquan Tian (Fish and Fisheries, 2025)
Fisheries bycatch poses one of the most significant threats to sea turtles. Although various methodologies have been developed to mitigate sea turtle bycatch in swordfish and tuna longline fisheries, the effectiveness and interactions remain uncertain. In this study, we conducted a comprehensive meta‐analysis, encompassing 41 studies focused on sea turtles and 36 studies on tunas, swordfish and sharks, all derived from well‐controlled experimental research in swordfish and tuna longline fisheries. The objective was to systematically evaluate the relative effectiveness of species‐specific mitigation strategies for sea turtles, particularly examining the impact of circle hooks and fish bait as alternatives to conventional longline fishing practices. While a nuanced hierarchy, characterised by species‐specific patterns, was observed among the mitigation measures, circle hooks demonstrated great promise in reducing bycatch of loggerhead, olive ridley and leatherback turtles, with minimal impact on the catch rates of tuna, swordfish and sharks. We highlighted the broader applicability of fish bait in minimising sea turtle bycatch, noting that the effectiveness of bait may overlap with that of hooks, potentially making the additional benefits of the hooks less evident. The study also revealed regional variations in the effectiveness of these methods, emphasising the need for more detailed data collection. Given current data limitations that restrict extensive meta‐analyses, a series of small‐sample studies with promising innovations, exemplified by circle hooks with a wire appendage and blue‐white lights, necessitates in‐depth investigation and field tests.

Occurrence and fate of atmospheric short/medium chain chlorinated paraffins: Size distribution and inhalation exposure - Naibing Liang; Rong Cao; Nan Jiang; Chengcheng Shi; Zhangpeng Guo; Yuan Gao; Ruiqin Zhang; Haijun Zhang; Jiping Chen; Ningbo Geng (Science of The Total Environment, 2024)

Evolution and health risk of indicator microorganisms in landscape water replenished by reclaimed water - Yitong Chen; Chang Qi; Yanan Yu; Xiaoxin Cao; Xiang Zheng; Rong Cheng (Journal of Environmental Sciences, 2024)

Immunoprotective effect of recombinant Lactobacillus plantarum expressing largemouth bass virus MCP on largemouth bass - Yong-Lei Yang; Rong-Rong Zhang; Jing-Yi Pang; Jun-Hong Xing; Tian-Kui Guo; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; Jian-Zhong Wang; Xin Cao; Nan Wang; et al. (Fish & Shellfish Immunology, 2024)

Block copolymer nanoparticles doping polyacrylonitrile membranes for efficient adsorption of water-soluble dyes from water - Rong Cao; Enyang Zhang; Yuan Liu; Axiang Li; Wangqing Zhang (Chemical Engineering Journal, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

Characterization and expression analysis of the MADS-box gene AGL8 in cotton: insights into gene function differentiation in plant growth and stress resistance - Zhicheng Wang; Yuefen Cao; Yurong Jiang; Mingquan Ding; Junkang Rong (Molecular Biology Reports, 2024)

Characterization and expression analysis of GLABRA3 (GL3) genes in cotton: insights into trichome development and hormonal regulation - Naisi Wu; Benyi Lu; YaSir Muhammad; Yaofen Cao; Junkang Rong (Molecular Biology Reports, 2024)

The GaKAN2, a KANADI transcription factor, modulates stem trichomes in Gossypium arboreum - Xujiao Ren; Luying Yang; Yasir Muhammad; Yuxing Xie; Xinyi Lin; Li Yu; Yuefen Cao; Mingquan Ding; Yurong Jiang; Junkang Rong (Molecular Genetics and Genomics, 2024)

Assessment of carbon emissions and reduction potential in China's copper smelting industry - Rong Gao; Yao Shi; Chun Cao; Huiquan Li; Yuanbo Xie; Jingjing Shi; Chenmu Zhang; Xue Guan (Journal of Industrial Ecology, 2024)
As the largest producer and consumer of copper, China is facing enormous challenges from carbon peaking and neutrality. This article adopts “bottom‐up” and “top‐down” methods to construct a more accurate model, to predict the CO 2 emissions of China's copper smelting industry, and explores its potential for carbon reduction in the future from three scenarios as the baseline scenario (BAU), the general low‐carbon (NLC), and the enhanced low‐carbon (ELC). The results show that the CO 2 emissions can achieve a peak in 2028 either in NLC or ELC scenarios, with a peak range of 14.9–16.88 million tonnes. Prior to reaching the peak, the contributions of energy adjustment, material substitution, and process selection to carbon reduction have significantly improved, and the contribution rates increased from 30.91%, 4.11%, and 1.46% to 42.7%, 32.07%, and 15.63% in ELC scenario. After the peak, the contribution of energy adjustment gradually slows down, while the material substitution continues to increase, and the contribution rates increased from 21.25% and 32.07% to 29.38% and 40.01% in NLC and ELC scenarios. In the future, concentrate oxygen‐enriched bottom‐blowing smelting and direct refining from waste copper anode furnaces show ideal potential for carbon reduction before 2025, increasing the proportion of recycled copper production, and adjusting energy structure will be more effective from 2025 to 2035. The conclusions of this study can provide a scientific basis for formulating policy recommendations for green and low‐carbon development of the copper industry in China and all over the world in the future.

Soil nutrient levels are associated with suppression of banana Fusarium wilt disease - Yifan Cao; Yannan Ou; Nana Lv; Chengyuan Tao; Hongjun Liu; Rong Li; Zongzhuan Shen; Qirong Shen (Soil Ecology Letters, 2024)

Host preference and mortality caused by the parasitoid Sclerodermus guani on different cerambycid species - Qun Yu; Shuang Li; Yu-Jun Kong; Zuo-Xiang Sun; Dan-Dan Cao; Jian-Rong Wei (BioControl, 2024)

FGTN: Fragment-based graph transformer network for predicting reproductive toxicity - Jia-Nan Ren; Qiang Chen; Hong-Yu-Xiang Ye; Cheng Cao; Ya-Min Guo; Jin-Rong Yang; Hao Wang; Muhammad Zafar Irshad Khan; Jian-Zhong Chen (Archives of Toxicology, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Quantitative evaluation of hydrate-based CO2 storage in unsealed marine sediments: Viewpoint from the driving force of hydrate formation and CO2-water contact ability - Hong-Nan Chen; Yi-Fei Sun; Wei-Xin Pang; Ming-Long Wang; Ming Wang; Jin-Rong Zhong; Liang-Liang Ren; Bo-Jian Cao; Dan Rao; Chang-Yu Sun; Guang-Jin Chen (Fuel, 2024)

Enhancing zinc-ion storage capacity of coal tar-derived porous carbon by functionalization and hierarchical structure design - Ruilun Xie; Guangming Rong; Ende Cao; Miaomiao Zhang; Xiangchun Liu; Zhao Lei; Tianyu Chen; Yujiao Tian (Fuel, 2024)

Investigating the temporal evolution of physicochemical attributes and flavorome profiles in Sichuan shai vinegar utilizing diverse aging techniques - Li Li; Cuixin Huang; Zhicheng Li; Yulin Zhao; Jun Liu; Yu Zheng; Rong Cao; Yuting Liao (Food Research International, 2024)

Gene expression profiles and metabolic pathways responsible for male sterility in cybrid pummelo - Rong Wang; Yang-Cao Shi; Bo Zhang; Wan-Rong Liu; Feng-Quan Tan; Fang Lu; Nan Jiang; Lai-Chao Cheng; Kai-Dong Xie; Xiao-Meng Wu; Wen-Wu Guo (Plant Cell Reports, 2024)

Effect of the spatial changes in engineering properties on municipal solid waste landfill slope stability - Rong Yang; Zengguang Xu; Junrui Chai; Cheng Cao; Jianxi Ren; Xiaoke Chang (Bulletin of Engineering Geology and the Environment, 2024)

Recent advances on shrimp paste: Key flavor components and biochemical formation pathways, biogenic amine formation, microbial functions, and innovative process strategies - Meng-Yue Hu; Ling Zhao; Hui-Hui Sun; Yong Xue; Xiang-Zhao Mao; Rong Cao (Trends in Food Science & Technology, 2024)

Obtaining phenolic-rich extracts from tree nut shells biomass by room temperature green extraction: Molecular insights and attribution analysis - Ruoyu Du; Zhaobao Xiang; Xue Yang; Xinling Zhao; Qingya Cao; Rong Peng; Guizhi Zhang; Zhongyi Yin (Sustainable Chemistry and Pharmacy, 2024)

Environmental high temperature affects pre-implantation embryo development by impairing the DNA repair ability - Si-Jing Qu; Shi-Yong Zhu; En-Yan Wang; Xin-Lei Yan; Rong-Feng Cao; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2024)

Lithium-ion battery future degradation trajectory early description amid data-driven end-of-life point and knee point co-prediction - Ganglin Cao; Yao Jia; Shouxuan Chen; Yuanfei Geng; Shuzhi Zhang; Haibin Lu; Rong Feng; Ning Wang; Xiongwen Zhang (Journal of Cleaner Production, 2024)

Macroaggregate is crucial in soil carbon and nitrogen accumulation under different vegetation types in the Loess Plateau, China - Hongjian Hao; Yujie Liang; Duo Pian; Ying Zhang; Yaxian Chen; Hongtao Lai; Zhouchang Yu; Ahejiang Sailike; Rong Wang; Ling Cao; Xinhui Han; Wei Zhang (Forest Ecology and Management, 2024)

Mitigation of malondialdehyde-induced protein lipoxidation by epicatechin in whey protein isolate - Wenhua Yao; Xingya Hao; Zhangjie Hu; Zhenghao Lian; Yue Cao; Rong Liu; Xiaoying Niu; Jun Xu; Qin Zhu (Food Chemistry, 2024)

Gum arabic coating alleviates chilling injury of cold-stored peach by regulating reactive oxygen species, phenolic, and sugar metabolism - Zengyu Gan; Yupei Zhang; Ziteng Jin; Yongjie Wang; Jiali Li; Caining Yang; Qing Cao; Jinyin Chen; Zhenbang Rong; Xuming Lu; Suqin Guo (Food Chemistry, 2024)

Fe-doping accelerated magnesium storage kinetics in rutile TiO2 cathode materials - Qianwei Zhang; Xin Liu; Changliang Du; Mingwei Jin; Lifen Yang; Rong Jiang; Xilan Ma; Youqi Zhu; Chuanbao Cao; Meishuai Zou (Chemical Engineering Journal, 2024)

Mitigating nitrite inhibition in Klebsiella strain denitrification: Stimulating endogenous driving force with microscale zero-valent iron - Wen-ying Cao; Kuang-di Xu; Su Zhang; Si-jia Li; Yi-cheng Yuan; Jing-xuan Lu; Lei Yu; Shao-hua Zhou; Jun-ting Gan; Quan Wang; Rong-ping Chen; Ke Yin (Chemical Engineering Journal, 2024)

Numerical study on thermal–hydraulic behaviors of a natural circulation system with petal-shaped fuel rod bundle - Jian-Chuang Sun; Rong-Jiang Zhou; Xiang-Fei Meng; Jin-Yi Cao; Wen-Chao Zhang; Jin-Cheng Wang; Wei-Hua Cai (Annals of Nuclear Energy, 2024)

Management of zooplanktonic predations for efficient and sustainable production of Arthrospira - Xiaobin Wen; Rongxiang Lü; Junying Zhu; Du Cao; Junfeng Rong; Weichun Du; Yeguang Li (Algal Research, 2024)

Physicochemical properties dominating the behaviors of short/medium chain chlorinated paraffins in the atmosphere - Zhijie Zhang; Ningbo Geng; Cuiping Ning; Xiuhua Zhu; Haijun Zhang; Jiping Chen; Rong Cao (Journal of Hazardous Materials, 2024)

p‑Phenylenediamine antioxidants in PM2.5: New markers for traffic in positive matrix factorization source apportionment - Nan Jiang; Xuexin Hao; Zichen Wang; Minzhen Li; Dong Zhang; Rong Cao; Ruiqin Zhang; Haijun Zhang; Jiping Chen; Ningbo Geng (Journal of Hazardous Materials, 2024)

Resident motivations, policy types and multisphere waste sorting intentions in China from a dual-interest integration perspective: An expanded goal-framing theory - Gai Cao; Peng Liu; Rong Cao (Environmental Impact Assessment Review, 2024)

TBC1D1 is an energy-responsive polarization regulator of macrophages via governing ROS production in obesity - Qi Wang; Ping Rong; Wen Zhang; Xinyu Yang; Liang Chen; Ye Cao; Minjun Liu; Weikuan Feng; Qian Ouyang; Qiaoli Chen; Hailong Li; Hui Liang; et al. (Science China Life Sciences, 2024)

The response of Martian photoelectron boundary to the 2018 global dust storm - Yuqi Wang; Jun Cui; Yong Wei; Zhaopeng Wu; Kai Fan; Zhaojin Rong; Fei He; Yutian Cao; Jiawei Gao (Science China Earth Sciences, 2024)

Basic study on cryopreservation of rat calvarial osteoblasts with different cryoprotectants - Xu Jiang; Tan Zhijian; Cao Min; Yu Rong; Tan Xinghui; Xin Gong (Cell and Tissue Banking, 2024)

Experimental research on pull-out behavior of steel-UHPC composite beams with new composite dowels connectors - Pin Zhao; Xudong Shao; Junhui Cao; Xueliang Rong (Engineering Structures, 2024)

Constructing Cu9S5@CuSe heterostructures under microwave irradiation for rechargeable magnesium batteries - Mingwei Jin; Zhaoyu Xue; Heng Cao; Qianwei Zhang; Rong Jiang; Changliang Du; Lifen Yang; Xilan Ma; Youqi Zhu; Meishuai Zou; Chuanbao Cao (Chemical Engineering Journal, 2024)

Adenylate kinase phosphate energy shuttle underlies energetic communication in flagellar axonemes - Huan Wu; Yanman Zhang; Yuqian Li; Shuya Sun; Jintao Zhang; Qingsong Xie; Yue Dong; Shushu Zhou; Xuan Sha; Kuokuo Li; Jinyi Chen; Xin Zhang; et al. (Science China Life Sciences, 2024)

Both Short-term and Long-term Ozone Pollution Alters the Chemical Composition of rice Grain - Guoyou Zhang; Xiaoya Pan; Yaxin Hu; Rong Cao; Qinan Hu; Rao Fu; Risalat Hamdulla; Bo Shang (Bulletin of Environmental Contamination and Toxicology, 2024)

Aqueous preparation of arginyl-fructosyl-glucose (a maltose-arginine AC) and determination of Amadori compounds (ACs) in red ginseng by ultra-high performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) - Jialing Cao; Rong Tsao; Cheng Yang; Lianfu Zhang (Food Research International, 2024)

Phyllanthus emblica Linn: A comprehensive review of botany, traditional uses, phytonutrients, health benefits, quality markers, and applications - Qin-Ge Ma; Lei Wang; Rong-Hua Liu; Jin-Bin Yuan; Hui Xiao; Zhang-Yang Shen; Jia-Xin Li; Jia-Zeng Guo; Lan Cao; Hui-Lian Huang; Rong-Rui Wei (Food Chemistry, 2024)

Porphyrin-based MOFs for sensing environmental pollutants - Pan Gao; Soumya Mukherjee; Mian Zahid Hussain; Song Ye; Xusheng Wang; Weijin Li; Rong Cao; Martin Elsner; Roland A Fischer (Chemical Engineering Journal, 2024)

Deciphering the stability mechanism of Pt-Ni/Al2O3 catalysts in syngas production via DRM - Rui Zhao; Kun Cao; Rongli Ye; Yuanting Tang; Chun Du; Fudong Liu; Yunkun Zhao; Rong Chen; Bin Shan (Chemical Engineering Journal, 2024)

Seasonality and potential generation mechanisms of submesoscale processes in the northern Bay of Bengal - Yifei Zhou; Wei Duan; Haijin Cao; Guidi Zhou; Rong Cui; Xuhua Cheng (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Polyoxovanadate Li7[V15O36(CO3)] and its derivative γ-LiV2O5 as superior performance cathode materials for aqueous zinc-ion batteries - Haoran Xiao; Xin Du; Rong Li; Hao Jin; Lingling Xie; Qing Han; Xuejing Qiu; Xinli Yang; Limin Zhu; Xiaoyu Cao (Chemical Engineering Journal, 2024)

A compound enzyme as an additive to a continuous anaerobic dynamic membrane bioreactor for enhanced lignocellulose removal from codigestion: Performance, membrane characteristics and microorganisms - Bao-Shan Xing; Xiang-Lin Chang; Yi Zhang; Sifan Cao; Xi-Fang Tang; Yong-Chen Han; Yu-You Li; Xiaochang C. Wang; Rong Chen (Bioresource Technology, 2024)

Size distribution and source-specific risks of atmospheric elements in Dalian, a coastal city in north China - Rong Cao; Fanyu Meng; A. Mila; Xiaoli Sun; Haijun Zhang; Jiping Chen; Ningbo Geng (Atmospheric Environment, 2024)

Taphonomy and Paleoecology of Lycoptera: A Case Study from the Lower Jehol Group in Western Liaoning, Northeastern China - Zhongwu Lan; Rong Cao; Shujing Zhang (Journal of Earth Science, 2024)

Radio frequency heating induced 3D printed white croaker (Argyrosomus argentatus) surimi gelation: Effectiveness and gel quality evaluation - Yaxing Yang; Feifan Cao; Rong Han; Feng Li; Hu Shi; Fanbin Kong; Yang Jiao (Innovative Food Science & Emerging Technologies, 2024)

Contact-electro-catalysis for degradation of trace antibiotics in wastewater - Da-Qi Cao; Rong-Kun Fang; Yi-Xuan Song; Ming-Guo Ma; Haiyan Li; Xiao-Di Hao; Rongling Wu; Xiangyu Chen (Chemical Engineering Journal, 2024)

Microwave-induced defect-rich vanadium sulfide cathodes for highly reversible electrochemical magnesium storage - Rong Jiang; Bolin Liu; Changliang Du; Mingwei Jin; Xin Liu; Xilan Ma; Youqi Zhu; Meishuai Zou; Chuanbao Cao (Chemical Engineering Journal, 2024)

Serum indoleamine 2, 3-dioxygenase and tryptophan-2, 3-dioxygenase: potential biomarkers for the diagnosis of major depressive disorder - Jun Liang; Zhuo-Yu Cheng; Feng Shan; Yin Cao; Qing-Rong Xia (Psychopharmacology, 2024)

Development of SV2A Ligands for Epilepsy Treatment: A Review of Levetiracetam, Brivaracetam, and Padsevonil - Peng-Peng Wu; Bi-Rong Cao; Fu-Yun Tian; Zhao-Bing Gao (Neuroscience Bulletin, 2024)

Efficient magnetic solid-phase extraction, UPLC-MS/MS detection, and consumption assessment of five trace psychoactive substances - Rong Zhu; Shurui Cao; Hongtao Su; Dewang Ming; Yao Tang; Zhiqiong Chen (Environmental Science and Pollution Research, 2024)

The double-edged effects of La2O3 and CeO2 on the performance of high-rate anaerobic sludge bed reactors and microbial mechanisms - Kai Su; Lin-xiao Li; Zhuo Zeng; Xue Yang; Tao Lei; Han Zhang; Qin Wang; Rong Cao (Process Safety and Environmental Protection, 2024)

Synchronous fluorescence spectra-based machine learning algorithm with quick and easy accessibility for simultaneous quantification of polycyclic aromatic hydrocarbons in edible oils - Jia-Wen Wei; Jia-Rong He; Shi-Yi Chen; Yi-Han Guo; Xuan-Zhu Huo; Nuan Zheng; Shuo-Hui Cao; Yao-Qun Li (Food Control, 2024)

Short-term effects of substrate surface structure on macroinvertebrates community structure and functional characteristics - Yufu Gao; Liping Rong; Xiangyu Zhao; Xinyue Wang; Chenlu Lin; Lina Cao; Haijun Yang (Ecological Engineering, 2024)

Impacts of land use and climate change on runoff in the Shaying River Basin based on SWAT model - Jie Tao; Yang Cao; Rong Gan; Qiting Zuo; Qingli Zhao; Yinxing He (Limnology, 2024)

Conductive nanofiltration membranes via in situ PEDOT-polymerization for electro-assisted membrane fouling mitigation - Tian-Zhi Jia; Ru Feng; Chun Cui; Qian Chen; Levente Cseri; Rong-Fei Zhou; Gyorgy Szekely; Xue-Li Cao; Shi-Peng Sun (Water Research, 2024)

Assessment of health risks associated with prediction of vegetable inorganic arsenic concentrations given different soil properties - Yi-Jie Liao; Yu-Rong Cao; Dar-Yuan Lee (Environmental Geochemistry and Health, 2024)

A nationwide investigation on the characteristics and health risk of trace elements in surface water across China - Fanyu Meng; Rong Cao; Xiuhua Zhu; Yuying Zhang; Manxue Liu; Jufang Wang; Jiping Chen; Ningbo Geng (Water Research, 2024)

Black shale LA-ICP-MS Rb-Sr and monazite SIMS U-Pb geochronology from the Cryogenian successions in the northern Yangtze Block - Zhongwu Lan; Kyle Larson; Rong Cao; Qin Ye; Jun Hu; Guoqiang Tang; Jiao Li; Jinnan Tong (Precambrian Research, 2024)

Numerical simulation-based hydrodynamic interaction of bottom-set gillnet with current and ecological implications - Shaojian Guo; Cheng Zhou; Rong Wan; Jie Cao; Yucheng Wang (Ocean Engineering, 2024)

Developing a highly efficient, environmentally friendly and cost-effective copper sulfide semiconductor sponge for nuclear wastewater treatment under one sun - Wencai Bai; Mengjiao Liu; Kaifu Yu; Xin Cao; Jie Lian; Zhibin Zhao; Yong Xiang; Baoliang Xu; Tao Chen; Rong He; Nan Sun; Wenkun Zhu (Journal of Environmental Chemical Engineering, 2024)

Residual levels and health risk assessment of trace metals in Chinese resident diet - Yubing Dai; Shuai Sun; Rong Cao; Haijun Zhang; Jiping Chen; Ningbo Geng (Journal of Environmental Sciences, 2024)

Shale oil potential and mobility in low- to medium-maturity lacustrine shales: A case study of the Yanchang Formation shale in southeast Ordos Basin, China - Huairen Cao; Jun Shi; Zhao-Wen Zhan; Hao Wu; Xiaoyu Wang; Xin Cheng; Haolin Li; Yan-Rong Zou; Ping'an Peng (International Journal of Coal Geology, 2024)

How hydrogen bonding and π–π interactions synergistically facilitate mephedrone adsorption by bio-sorbent: An in-depth microscopic scale interpretation - Shurui Cao; Rong Zhu; Duanhao Wu; Hongtao Su; Zhenghong Liu; Zhiqiong Chen (Environmental Pollution, 2024)

Molecular dynamics simulation and experimental analysis of nucleation and growth mechanism of mixed inorganic salts in supercritical water - Siqi Rong; Ruoyu Wang; Anlan Xie; Zhiyong Peng; Peng Cao; Mingyi Zhang; Jinhua Cui; Yunan Chen; Liejin Guo (Chemical Engineering Journal, 2024)

Enhancing the removal of chlorinated hydrocarbons from groundwater using a new BL5 microorganism with functional CS@ZVI materials - Zhiguo Chen; Wenqing Cao; Yan Li; Jingpeng Song; Yiyun Liu; Juncheng Liu; Rong Zhang; Rongxin Su; He Bai (Journal of Water Process Engineering, 2024)

Synthesis of an autochthonous microbial community by analyzing the core microorganisms responsible for the critical flavor of bran vinegar - Li Li; Na Li; Junjie Fu; Jun Liu; Xue Ping Wen; Hong Cao; Hongwei Xu; Ying Zhang; Rong Cao (Food Research International, 2024)

Using geodetic measurements derived terrestrial water storage to investigate the characteristics of drought in Yunnan, China - Chao Chen; Rong Zou; Zhiwei Fang; Jiaming Cao; Qi Wang (GPS Solutions, 2024)
The use of the global navigation satellite system (GNSS) for monitoring changes in terrestrial water storage (TWS) is growing. However, the density of GNSS stations is sparse in most areas, and the widely used Green’s function (GF) method cannot provide a satisfactory resolution for inversion problems. As the Slepian basis function (SBF) method has been successfully used for gravity inversions, GNSS geodesists have recently applied the SBF method to GNSS displacements. However, the evaluation of TWS differences inferred from GNSS using the SBF and the GF has been rarely assessed. In this study, we use both the GF and the SBF methods to investigate the TWS in Yunnan by using more than ten years (2010–2021) of GNSS observations. We observe a remarkable consistency between the two inversion methods employed for GNSS data, as well as a strong agreement with equivalent water heights (EWH) inferred from the Gravity Recovery and Climate Experiment (GRACE) and GRACE Follow-On (GFO), hydrological model (GLDAS-NOAH), and precipitation data, despite variations in the amplitude. Furthermore, affected by monsoon climate and topography, Yunnan is prone to drought. We analyze the main nine drought events, evaluate the connection between GNSS-inverted TWS during 2010–2021, and find that almost all droughts in Yunnan occurred during the "trough period" within the GNSS-DSI.

Underwater Object Detection in Marine Ranching Based on Improved YOLOv8 - Rong Jia; Bin Lv; Jie Chen; Hailin Liu; Lin Cao; Min Liu (Journal of Marine Science and Engineering, 2023)
The aquaculture of marine ranching is of great significance for scientific aquaculture and the practice of statistically grasping existing information on the types of living marine resources and their density. However, underwater environments are complex, and there are many small and overlapping targets for marine organisms, which seriously affects the performance of detectors. To overcome these issues, we attempted to improve the YOLOv8 detector. The InceptionNeXt block was used in the backbone to enhance the feature extraction capabilities of the network. Subsequently, a separate and enhanced attention module (SEAM) was added to the neck to enhance the detection of overlapping targets. Moreover, the normalized Wasserstein distance (NWD) loss was proportionally added to the original CIoU loss to improve the detection of small targets. Data augmentation methods were used to improve the dataset during training to enhance the robustness of the network. The experimental results showed that the improved YOLOv8 achieved the mAP of 84.5%, which was an improvement over the original YOLOv8 of approximately 6.2%. Meanwhile, there were no significant increases in the numbers of parameters and computations. This detector can be applied on platforms for seafloor observation experiments in the field of marine ranching to complete the task of real-time detection of marine organisms.

LC-MS-based untargeted metabolomics reveals the mechanism underlying prostate damage in a type 2 diabetes mouse model - Rong Qi; Shao-san Kang; Yongchao Pei; Mingming Liu; Yufan Zhou; Bo Guan; Xinduo Zhang; Zhiguo Li; Fenghong Cao (Reproductive Biology, 2023)

Modeling the long-term transport and fate of oil spilled from the 2021 A Symphony tanker collision in the Yellow Sea, China: Reliability of the stochastic simulation - Ruichen Cao; Zengrui Rong; Haibo Chen; Yi Liu; Lin Mu; Xianqing Lv (Ocean Modelling, 2023)

Insight into personal exposure characteristics and health effects of PM2.5 and PM0.25-bound PAHs and their derivatives with different heating ways in the Fenwei Plain, China - Yunxuan Gu; Hongmei Xu; Rong Feng; Bin Zhang; Min Gao; Jian Sun; Zhenxing Shen; Linli Qu; Steven Sai Hang Ho; Junji Cao (Environmental Pollution, 2023)

Effects of PM2.5 emissions from household fuel combustion on biomarkers and pulmonary function in rural areas of Fenwei Plain, China - Rong Feng; Hongmei Xu; Hongwei Lu; Bei Han; Yue Cheng; Yunxuan Gu; Jian Sun; Liu Yang; Zhenxing Shen; Junji Cao (Atmospheric Pollution Research, 2023)

The expression of CD86 in CD3+CD56+ NKT cells is associated with the occurrence and prognosis of sepsis-associated encephalopathy in sepsis patients: a prospective observational cohort study - Sheng-long Chen; Xiao-yu Liu; Jun-hong Huang; Lu-hua Xian; Xu-sheng Li; Kang-rong Wang; Jing Li; Tian-cao Zhang; Guo-ge Huang; Xin-qiang Liu; Hong-ke Zeng; Mao-hua Zhou; et al. (Immunologic Research, 2023)

Calcite U-Pb Geochronology Revealing Late Ediacaran–Early Paleozoic Hydrothermal Alteration in the Stenian-Tonian Carbonate of Northeastern North China Craton - Rong Cao; Hanqing Zhao; Zhongwu Lan (Journal of Earth Science, 2023)

The influence of dust on extreme precipitation at a large city in North China - Taichen Feng; Tiangang Yuan; Jiahui Cao; Zhikuan Wang; Rong Zhi; Zhiyuan Hu; Jianping Huang (Science of The Total Environment, 2023)

Current status, future prediction and offset potential of fossil fuel CO2 emissions in China - Jiaxi Cao; Jian Zhang; Ye Chen; Rong Fan; Lei Xu; Entao Wu; Yuan Xue; Junliu Yang; Yiming Chen; Bo Yang; Shuhong Wu (Journal of Cleaner Production, 2023)

Adaptability law of central heating environment under the effect of thermal history: A continuous field survey - Chao Jia; Xihao Bie; Chang Sun; Zhicheng Zhang; Yonghua Rong; Jing Cao; Menghan Wang (Building and Environment, 2023)

Fine mapping and candidate gene analysis of a novel fertility restorer gene for C-type cytoplasmic male sterility in maize (Zea mays L.) - Peng Zhang; Zhuofan Zhao; Mingmin Zheng; Yongming Liu; Qunkai Niu; Xiaowei Liu; Ziwen Shi; Hongyang Yi; Tao Yu; Tingzhao Rong; Moju Cao (Theoretical and Applied Genetics, 2023)

Linear relationship between CH4 fluxes and atmospheric CO2 concentration levels controlled by rice biomass and soil methanogenic communities - Yuanyuan Wang; Zhenghua Hu; Shuqi He; Qiang Jing; Lidong Shen; Chao Liu; Zhurong Wu; Wei Huang; Guihua Lu; Rui Cao; Kezhi Zheng; Ning Dong; et al. (Nutrient Cycling in Agroecosystems, 2023)

Quantification of multiple environmental controls on lipid biomarkers in common marine diatoms and dinoflagellates - Zhong Cao; Rong Bi; Chuanli Zhang; Jiaxuan Cui; Li Li; Yang Ding; Meixun Zhao (Marine Biology, 2023)

In-situ constructing amidoxime groups on metal-free g-C3N4 to enhance chemisorption, light absorption, and carrier separation for efficient photo-assisted uranium(VI) extraction - Kaifu Yu; Yi Li; Xin Cao; Ruixiang Wang; Li Zhou; Linzhen Wu; Ningning He; Jia Lei; Dengjiang Fu; Tao Chen; Rong He; Wenkun Zhu (Journal of Hazardous Materials, 2023)

Converting coastal silt into subgrade soil with biochar as reinforcing agent, CO2 adsorbent, and carbon sequestrating material - Shuwei Fang; Ling Zhao; Guoqiang Rong; Bing Chen; Xiaoyun Xu; Hao Qiu; Xinde Cao (Journal of Environmental Management, 2023)

High-accuracy lunar global brightness-temperature mapping using third-order Fourier fitting and co-kriging interpolation - Yongjiu Feng; Yuze Cao; Xiaohua Tong; Peiqi Wu; Shurui Chen; Pengshuo Li; Mengrong Xi; Zhenkun Lei; Rong Wang (Icarus, 2023)

A self-assembled nanoparticle vaccine based on pseudorabies virus glycoprotein D induces potent protective immunity against pseudorabies virus infection - Xujiao Ren; Nan Cao; Linxing Tian; Wenqiang Liu; Hechao Zhu; Zhenxiang Rong; Manman Yao; Xiangmin Li; Ping Qian (Veterinary Microbiology, 2023)

Identification and evaluation of a novel PARP1 inhibitor for the treatment of triple-negative breast cancer - Rong Gong; ZhongYe Ma; LinHao He; ShiLong Jiang; DongSheng Cao; Yan Cheng (Chemico-Biological Interactions, 2023)

Simultaneous removal of sulfamethoxazole during fermentative production of short-chain fatty acids - Yue Wang; Rongrong Lin; Yushuang Cao; Shuangfei Li; Rong Cui; Wanqian Guo; Shih-Hsin Ho; Yoong Kit Leong; Duu-Jong Lee; Jo-Shu Chang (Bioresource Technology, 2023)

CLASRP oncogene as a novel target for colorectal cancer - Quan Gu; Jianzhong Wu; Heng Xu; Haixia Cao; Junying Zhang; Changwen Jing; Zhuo Wang; Mengjie Du; Rong Ma; Jifeng Feng (Functional & Integrative Genomics, 2023)
Clk4-associated serine/arginine-rich protein ( CLASRP ), an alternative splicing regulator, may be involved in the development and progression of cancer by regulating the activity of the CDC-like kinase (Clk) family. This study explored the biological function of CLASRP in colorectal cancer (CRC). The expression of CLASRP , which is associated with clinicopathological features, was analysed in CRC tissues and paired noncancer tissues by RT–PCR. The roles of CLASRP were investigated in CRC cells transfected with plasmids or shRNA through proliferation, migration and invasion assays in vitro and a xenograft model in vivo . Apoptosis was analysed using CLASRP -overexpressing CRC cells by western blotting. Clk inhibitors were used to perform functional research on CLASRP in CLASRP -overexpressing CRC cells. CLASRP was significantly upregulated in CRC cell lines, while high CLASRP expression was correlated with metastasis in CRC patients. Functionally, overexpression of CLASRP significantly promoted the proliferation, migration and invasion of CRC cells in vitro and tumour growth in vivo. Mechanistically, the proliferation, migration and invasion of CLASRP -overexpressing CRC cells were inhibited by Clk inhibitors, accompanied by low expression of CLASRP at the gene and protein levels. Clk inhibitors induced apoptosis of CLASRP -overexpressing CRC cells, resulting in direct blockade of cell growth. The expression levels of cleaved caspase 3 and cleaved caspase 8 were increased in CLASRP -overexpressing CRC cells treated with Clk inhibitors. CLASRP might serve as a promotional oncogene in CRC cells and be suppressed by Clk inhibitors through activation of caspase pathways.

Relationship between daily variations of methane emissions and eructation peaks in dairy cows measured with an automated head-chamber system - Rong Wang; Yu Rong Cao; Xiu Min Zhang; Fan Zhang; Xu Tian; Rong Zhen Zhong; Zhi Liang Tan; Min Wang (Animal Feed Science and Technology, 2023)

Environmental and health impacts of household energy conversion on PAHs and their derivatives in PM2.5 in typical areas of northern China - Yunlong Bai; Hongmei Xu; Rong Feng; Yunxuan Gu; Meixuan Liu; Jian Sun; Linli Qu; Steven Sai Hang Ho; Zhenxing Shen; Junji Cao (Science of The Total Environment, 2023)

Ejiao peptide-iron chelates regulate the metabolism of iron deficiency anemia mice and improve the bioavailability of iron - Xiang-Rong Cheng; Yu-Yao Chen; Cong-Cong Cao; Jia-Hui Ma; Chen-Xi Zhang; Zi-Wei Zhao; Qian Wu; Yuan-Yuan Li; Mitchell N. Muskat; Guo-Qing Wu (Food Bioscience, 2023)

Chemical composition and potential health risks of tire and road wear microplastics from light-duty vehicles in an urban tunnel in China - Meixuan Liu; Hongmei Xu; Rong Feng; Yunxuan Gu; Yunlong Bai; Ningning Zhang; Qiyuan Wang; Steven Sai Hang Ho; Linli Qu; Zhenxing Shen; Junji Cao (Environmental Pollution, 2023)

NKD1 targeting PCM1 regulates the therapeutic effects of homoharringtonine on colorectal cancer - Jia Cao; Xiang Tao; Bin Shi; Jia Wang; Rong Ma; Jufen Zhao; Jinhai Tian; Qi Huang; Jingjing Yu; Libin Wang (Molecular Biology Reports, 2023)

Effects of discharge angle of jet from a slot orifice on cooling performance for a perforated air ducting system in dairy cattle barn - Mengbing Cao; Ruimin Yang; Christopher Y. Choi; Li Rong; Guoqiang Zhang; Kaiying Wang; Xiaoshuai Wang (Computers and Electronics in Agriculture, 2023)

Interspecies calibration for biomonitoring metal contamination in coastal waters using oysters and mussels - Xue Cao; Guangbin Zhong; Ke Pan; Jing Qian; Minwei Xie; Rong Chen; Yongyan Liao; Qiao-Guo Tan (Science of The Total Environment, 2023)

Long-term in-situ starvation and reactivation of co-digestion with food waste and corn straw in a continuous AnDMBR: Performance, sludge characteristics, and microorganism community - Bao-Shan Xing; Xiang-Lin Chang; Sifan Cao; Dong Wu; Yi Zhang; Xi-Fang Tang; Yu-You Li; Xiaochang C. Wang; Rong Chen (Science of The Total Environment, 2023)

Characteristics and comparisons of the aerobic and anaerobic denitrification of a Klebsiella oxytoca strain: Performance, electron transfer pathway, and mechanism - Cheng-jia Ju; Shareen Niyazi; Wen-yin Cao; Quan Wang; Rong-ping Chen; Lei Yu (Journal of Environmental Management, 2023)

A spatial downscaling method for multielement meteorological data: case study from a water conservation area of the upper Yellow River basin - Ying Cao; Biao Zeng; Fuguang Zhang; Yanqi Shen; Zhenhua Meng; Rong Jiang (Theoretical and Applied Climatology, 2023)

Characteristics of PM2.5 and Its Reactive Oxygen Species in Heating Energy Transition and Estimation of Its Impact on the Environment and Health in China—A Case Study in the Fenwei Plain - Zexuan Wang; Hongmei Xu; Rong Feng; Yunxuan Gu; Jian Sun; Suixin Liu; Ningning Zhang; Dan Li; Tao Wang; Linli Qu; Steven Sai Hang Ho; Zhenxing Shen; et al. (Advances in Atmospheric Sciences, 2023)

Failure criterion of double-plate vertically loaded anchor in saturated marine fine sand under monotonic loading - Guoqi Xing; Lijun Zhang; Yupeng Cao; Wei Xuan; Xiaotong Zhang; Rong Wang (Marine Georesources & Geotechnology, 2023)

Urban particulate water-soluble organic matter in winter: Size-resolved molecular characterization, role of the S-containing compounds on haze formation - Cuiping Ning; Yuan Gao; Haijun Zhang; Haoran Yu; Rong Cao; Jiping Chen (Science of The Total Environment, 2023)

Rare earth elements detoxification mechanism in the hyperaccumulator Dicranopteris linearis: [silicon-pectin] matrix fixation - Hong-Xiang Zheng; Yu-Lu Yang; Wen-Shen Liu; Ying Zhong; Yue Cao; Rong-Liang Qiu; Chong Liu; Antony van der Ent; Martin J. Hodson; Ye-Tao Tang (Journal of Hazardous Materials, 2023)

Dispersed Pd/alumina catalyst with finite iodine entry for boosted CO purification and dimethyl carbonate synthesis - Yun-Yun Zeng; Lu-Yang Qiao; Shan-Shan Zong; Rong Guo; Jian-Kai Cheng; Xin-Yi Cao; Zhang-Feng Zhou; Mao-Hong Fan; Yuan-Gen Yao (Chemical Engineering Journal, 2023)

Coaxial electrospun nanofibrous substrates with tunable wettability for constructing cucurbit[n]uril-embedded organic solvent nanofiltration membranes - Qian Wang; Qin-Yuan He; Liu-Lin Zhao; Yue Wang; Rong Fang; Cong Luo; Wei-Tong Lu; Hong-Ya Jiang; Shi-Peng Sun; Xue-Li Cao (Chemical Engineering Journal, 2023)

Dynamic responses of root vigor, lipid peroxidation and antioxidant enzymes in Artemisia selengensis to long-term drought and re-watering - Hui-xiong Huang; Yun Cao; Kai-jing Xin; Rong-hua Liang; Yi-ting Chen; Jia-jun Qi (Aquatic Ecology, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Computational design of deep eutectic solvent functionalized ZIF-8/biochar with high selectivity for mephedrone: Experimental validation and microscopic mechanism - Rong Zhu; Shurui Cao; Jie Tian; Mengni Luo; Jiade You; Zhiqiong Chen (Journal of Cleaner Production, 2023)

The effects of porous medium parameters on electroseismic conversion - Rong Peng; Feng Gao; Zichun Liu; Yuhan Sun; Dianhua Cao; Bangrang Di; Jianxin Wei (Journal of Applied Geophysics, 2023)

Phytoplankton community changes in a coastal upwelling system during the last century - Peng Peng; Rong Bi; Julian P. Sachs; Jie Shi; Yifei Luo; Weifang Chen; Chih-An Huh; Meng Yu; Yali Cao; Yaoyao Wang; Zhong Cao; Xiaohan Bao; et al. (Global and Planetary Change, 2023)

Plant succession and geo-topography determined forest soil P and nine fraction-Ps across a larch forest chronosequence in the northmost region of China - Xudong Cao; Qianru Ji; Chenhui Wei; Lu Xiao; Peng Zhang; Rong Mao; Xingyuan He; Wenjie Wang (Plant and Soil, 2023)

Essential Trace Element Status in Systemic Lupus Erythematosus: a Meta-analysis Based on Case-Control Studies - Hua Wang; Xian-Bao Li; Rong-Gui Huang; Nv-Wei Cao; Hong Wu; Kai-Di Li; Yi-Yu Wang; Bao-Zhu Li (Biological Trace Element Research, 2023)

Insight into the effects and mechanism of cellulose and hemicellulose on anaerobic digestion in a CSTR-AnMBR system during swine wastewater treatment - Yuzheng Wang; Yuqi Chen; Hongyu Xie; Wenzhi Cao; Rong Chen; Zhe Kong; Yanlong Zhang (Science of The Total Environment, 2023)

Retraction Note: Emerging protective roles of shengmai injection in septic cardiomyopathy in mice by inducing myocardial mitochondrial autophagy via caspase-3/Beclin-1 axis - Yan Cao; Xiaotong Han; Hongwei Pan; Yu Jiang; Xiang Peng; Weiwei Xiao; Jingjing Rong; Fang Chen; Jin He; Lianhong Zou; Yi Tang; Yanfang Pei; et al. (Inflammation Research, 2023)

Comparison between human olfactory sensitivity in the fasted and fed states: A systematic review and meta-analysis - Haoyu Nie; Rong Zhao; Yun Ai; Yingkai Yang; Bing Cao; Pengfei Han (Appetite, 2023)

A 40 % paddy surface soil organic carbon increase after 5-year no-tillage is linked with shifts in soil bacterial composition and functions - Jian-Ying Qi; Xiang-Bin Yao; Jian Lu; Long-Xin He; Jun-Li Cao; Zheng-Rong Kan; Xing Wang; Sheng-Gang Pan; Xiang-Ru Tang (Science of The Total Environment, 2023)

Resource utilization and development of phosphogypsum-based materials in civil engineering - Xiantao Qin; Yihu Cao; Haowei Guan; Qisheng Hu; Zhihao Liu; Jing Xu; Bo Hu; Zeyu Zhang; Rong Luo (Journal of Cleaner Production, 2023)

A novel multistage anoxic/aerobic process with sludge regeneration zone (R-MAO) for advanced nitrogen removal from domestic sewage - Lin Cao; Rong Sun; Wenyi Dong; Hongjie Wang; Zhongyi Dai; Xue Wang; Jin Xie; Hua Li (Journal of Environmental Sciences, 2023)

Magnetic metal–organic frameworks as adsorbents for the detection of azo pigments in food matrices - Lei Cheng; Rong Huang; Qiang Cao; Na Liu; Peiyi Li; Mengmeng Sun; Haiyang Qin; Lidong Wu (Food Chemistry, 2023)

Rapid charge transfer in covalent organic framework via through-bond for enhanced photocatalytic CO2 reduction - Li-Juan Gong; Li-Yao Liu; Shao-Shuai Zhao; Shuai-Long Yang; Duan-Hui Si; Qiu-Jin Wu; Qiao Wu; Yuan-Biao Huang; Rong Cao (Chemical Engineering Journal, 2023)

An “all in one” strategy to boost antibacterial phototherapy via porphyrin and boron dipyrromethenes based covalent organic framework - Shao–Shuai Zhao; Xue-Ping Guo; Xiao-Hong Pan; Yuan–Biao Huang; Rong Cao (Chemical Engineering Journal, 2023)

Deposition effect of inhaled particles in the human: Accurate health risks of personal exposure to PAHs and their derivatives from residential solid fuel combustion - Rong Feng; Hongmei Xu; Yunxuan Gu; Min Gao; Yunlong Bai; Meixuan Liu; Zhenxing Shen; Jian Sun; Linli Qu; Steven Sai Hang Ho; Junji Cao (Atmospheric Environment, 2023)

Short-Term Limited Water Irrigation Influences the Photosynthetic Pigments, Enzymatic and Non-Enzymatic Activities in Saccharum spontaneum L. at Vegetative Stage - Zhi-Nian Deng; Hai-Rong Huang; Cheng-Mei Huang; Krishan K. Verma; Hai-Bin Luo; Sheng-Li Jiang; Yi-Jie Li; Hui-Qing Cao; Kai-Chao Wu; Lin Xu (Sugar Tech, 2023)

A multicentre study on the incidence of respiratory viruses in children with community-acquired pneumonia requiring hospitalization in the setting of the zero-COVID policy in China - Ziheng Feng; Baoping Xu; Lili Zhong; Jing Chen; Jikui Deng; Zhengxiu Luo; Lingfeng Cao; Yu Tang; Changchong Li; Rong Jin; Li Deng; Yunxiao Shang; et al. (Archives of Virology, 2023)
Background Stringent nonpharmaceutical interventions (NPIs) have been implemented worldwide to combat the COVID-19 pandemic, and the circulation and seasonality of common respiratory viruses have subsequently changed. There have been few multicentre studies or comparisons of the prevalence of respiratory viruses accounting for community-acquired pneumonia (CAP) in hospitalized children between the pre-COVID period and the period after community and school reopening in the setting of the zero-COVID policy. Methods We included 1543 children with CAP who required hospitalization from November 1, 2020 to April 30, 2021 (period 1), and 629 children with the same conditions from November 1, 2018, to April 30, 2019 (period 2), in our study. All respiratory samples from these patients were screened for six respiratory viruses (respiratory syncytial virus [RSV], adenovirus [ADV], influenza A virus [Flu A], influenza B virus [Flu B], parainfluenza virus type 1 [PIV1], and parainfluenza virus type 3 [PIV3]) using a multiplex real-time PCR assay. Results and conclusions The median ages of the enrolled patients at the time of diagnosis were 1.5 years and 1.0 years for period 1 and period 2, respectively. In period 1, viral pathogens were detected in 50.3% (776/1543) of the enrolled patients. The most frequently identified viral pathogen was RSV (35.9%, 554/1543), followed by PIV3 (9.6%, 148/1543), PIV1 (3.6%, 56/1543), ADV (3.4%, 52/1543), Flu A (1.0%, 16/1543), and Flu B (0.8%, 13/1543). The total detection rates of these six viruses in the peak season of CAP were at the pre-COVID level. The prevalence of Flu A decreased dramatically, and circulation activity was low compared to pre-COVID levels, while the incidence of PIV3 increased significantly. There were no significant differences in the detection rates of RSV, ADV, Flu B, and PIV1 between the two periods. Our results showed that respiratory viruses accounted for CAP in hospitalized children at pre-COVID levels as communities and schools reopened within the zero-COVID policy, although the prevalence aetiology spectrum varied.

Mutualistic microbial community of Bacillus amyloliquefaciens and recombinant Yarrowia lipolytica co-produced lipopeptides and fatty acids from food waste - Song Bai; Bin Qiao; Zheng-Jie Hou; Geng-Rong Gao; Chun-Yang Cao; Jing-Sheng Cheng; Ying-Jin Yuan (Chemosphere, 2023)

Zinc finger protein 671 has a cancer-inhibiting function in colorectal carcinoma via the deactivation of Notch signaling - Yan Wang; Fen-rong Chen; Chong-cao Wei; Lin-lang Sun; Chen-yu Liu; Long-bao Yang; Xiao-yan Guo (Toxicology and Applied Pharmacology, 2023)

Trace elements in red swamp crayfish (Procambarus clarkii) in China: Spatiotemporal variation and human health implications - Hui Li; Huaiyan Li; Haiting Zhang; Jing Cao; Tao Ge; Jiale Gao; Yan Fang; Wenling Ye; Ting Fang; Yanhong Shi; Rong Zhang; Xinju Dong; et al. (Science of The Total Environment, 2023)

Associations of personal exposure to domestic heating and cooking fuel emissions and epidemiological effects on rural residents in the Fenwei Plain, China - Yunxuan Gu; Hongmei Xu; Rong Feng; Yue Cheng; Bei Han; Kin Fai Ho; Zexuan Wang; Yansu He; Linli Qu; Steven Sai Hang Ho; Jian Sun; Zhenxing Shen; et al. (Science of The Total Environment, 2023)

Dose–response mapping of MEHP exposure with metabolic changes of trophoblast cell and determination of sensitive markers - Yiwei Fang; Zhiliang Chen; Jinyu Chen; Minqi Zhou; Yuanyao Chen; Rong Cao; Chunyan Liu; Kai Zhao; Min Wang; Huiping Zhang (Science of The Total Environment, 2023)

A ca. 290 Ma hydrothermal calcite in Cambrian dolostone - Zhongwu Lan; Shitou Wu; Fangyue Wang; Bo Liu; Kaibo Shi; Jing Sun; Rong Cao; Xian-Hua Li (Marine and Petroleum Geology, 2023)

Multicopper oxidases GbAO and GbSKS are involved in the Verticillium dahliae resistance in Gossypium barbadense - Fei Wang; Tianxin Lu; Liping Zhu; Aiping Cao; Shuangquan Xie; Xifeng Chen; Haitao Shen; Quanliang Xie; Rong Li; Jianbo Zhu; Xiang Jin; Hongbin Li (Journal of Plant Physiology, 2023)

A study on molecular structural evolution of type II kerogen in a gold tube thermal system: Insights from solid-state 13C NMR - Deping Zhang; Huairen Cao; Yan Lei; Hao Wu; Xiaoyu Wang; Xuelian Guo; Jianping Yan; Shuhua Wang; Tianchi Shi; Haolin Li; Yan-rong Zou; Ping'an Peng (Fuel, 2023)

An approach to the high efficient exploitation of nature gas hydrate and carbon sequestration via injecting CO2/H2 gas mixture with varying composition - Bo-Jian Cao; Yi-Fei Sun; Hong-Nan Chen; Jin-Rong Zhong; Ming-Long Wang; Meng-Ya Niu; Jing-Yu Kan; Chang-Yu Sun; Dao-Yi Chen; Guang-Jin Chen (Chemical Engineering Journal, 2023)

Carbonate nanophase guided by terminally functionalized polyisoprene leading to a super tough, recyclable and transparent rubber - Mo-Kun Chen; Yi-Hai Zhao; Rong Zhang; Ying Yang; Jian Cao; Mao-Zhu Tang; Guangsu Huang; Yun-Xiang Xu (Chemical Engineering Journal, 2023)

Molecular Characterization and Dietary Regulation of Glutaminase 1 (gls1) in Triploid Crucian Carp (Carassius auratus) - Yangbo Xiao; Rong Huang; Shenping Cao; Dafang Zhao; Zhuangwen Mao; Chuchu Xiao; Zhehua Xu; Xiaomei Zhou; Xinran Zhang; Yu Zhang; Jianzhou Tang; Junyan Jin; et al. (Fishes, 2022)
Kidney-type glutaminase, encoded by the gls1 gene, plays a critical role in glutamate production and improvement of meat flavor. In this study, a gls1 gene encoding 595 amino acids was cloned from triploid crucian carp (Carassius auratus) (TCC) and showed a high similarity with the gls1 gene found in Cyprinus carpio, Sinocyclocheilus rhinocerous and Puntigrus tetrazona. Comparing the abundance of gls1 in different tissues, we found its expression level in the brain and liver were significantly higher than that in heart, gut, kidney, spleen and muscle. gls1 expression in the brain reached the highest value. In addition, the expression levels of gls1 also appeared different in diurnal variation, with the highest expression seen at 9:00, while it was low at 3:00, 6:00, 15:00 and 24:00. Furthermore, dietary regulation of gls1 expression was investigated in our study. In each feeding trial, each diet was randomly assigned to triplicate tanks. Fish were fed one of the tested diets up to satiation twice daily. The results showed that gls1 expression increased in 32% protein group and decreased in 35–41% protein group. The results of different protein source experiments showed that the expression of gls1 gene in the mixed protein group (the control group) was significantly higher than that in the fish meal and soybean meal groups. Glutamate treatment revealed that appropriate concentrations (0.10 mg/mL in vivo and 2.00% in vitro) of glutamate remarkably improved the expression of gls1. Besides, diets supplemented with 0.80–1.60% lysine-glutamate dipeptide exhibited a down regulatory impact on gls1 expression. In conclusion, this study demonstrated that the expression of gls1 in TCC was increased by 32% protein diet, mixed protein source diet and diet with 2.00% glutamate concentration, while decreased by 0.80–1.60% lysine-glutamate dipeptide. The findings of this study provide a reference for the regulation of gls1 and have a potential application in the optimization of dietary formula in aquaculture.

Comparison of Flavor Substances in Dried Shrimp Products Processed by Litopenaeus Vannamei from Two Aquaculture Patterns - Mengyue Hu; Yong Xue; Ling Zhao; Qi Liu; Rong Cao (Journal of Ocean University of China, 2022)

Ginsenoside Rb1 inhibits oxidative stress-induced ovarian granulosa cell injury through Akt-FoxO1 interaction - Ping Zhou; Feng Deng; Zi Yang; Canhui Cao; Hongcui Zhao; Fenting Liu; Ke Zhong; Lin Fu; Tianliu Peng; Di Sun; Hui Liu; Rong Li; et al. (Science China Life Sciences, 2022)

Plantlet regeneration from apple (Malus × domestica Borkh.) anther culture derived embryos - Chunfen Zhang; Shu Deng; Qiufen Cao; Sadao Komori; Rong Xiao (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

GDH promotes isoprenaline-induced cardiac hypertrophy by activating mTOR signaling via elevation of α-ketoglutarate level - Zhi-Rong Lin; Zhen-Zhen Li; Yan-Jun Cao; Wen-Jing Yu; Jian-Tao Ye; Pei-Qing Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)

Homozygous missense mutation in CCDC155 disrupts the transmembrane distribution of CCDC155 and SUN1, resulting in non-obstructive azoospermia and premature ovarian insufficiency in humans - Huan Wu; Xin Zhang; Rong Hua; Yuqian Li; Li Cheng; Kuokuo Li; Yiyuan Liu; Yang Gao; Qunshan Shen; Guanxiong Wang; Mingrong Lv; Yuping Xu; et al. (Human Genetics, 2022)

Moderate exercise relieves fluoride-induced liver and kidney inflammatory responses through the IKKβ/NFκB pathway - Yanghuan Yu; Ruiyan Niu; Fangye Zhao; Yangfei Zhao; Jinglu Wang; Jixiang Wang; Qiqi Cao; Rong Fu; Mohammad Hassan Nateghahmadi; Zilong Sun (Environmental Science and Pollution Research, 2022)

Cadmium exposure and the risk of GDM: evidence emerging from the systematic review and meta-analysis - Minqi Zhou; Lianqi Peng; Jingming Wang; Rong Cao; Zixuan Ou; Yiwei Fang (Environmental Science and Pollution Research, 2022)

Discrepancies in Simulated Ocean Net Surface Heat Fluxes over the North Atlantic - Chunlei Liu; Yazhu Yang; Xiaoqing Liao; Ning Cao; Jimmy Liu; Niansen Ou; Richard P. Allan; Liang Jin; Ni Chen; Rong Zheng (Advances in Atmospheric Sciences, 2022)

Preparation of Pinocembrin-Loaded F127/MPEG-PDLLA Polymer Micelles and Anti-Osteoporotic Activity - Xia Cao; Qing He; Michael Adu-Frimpong; Xinyi Shen; Wanjing Rong; Xiaoxiao Li; Jian Zhang; Xiaoli Xia; Feng Shi; Hao Ji; Elmurat Toreniyazov; Qilong Wang; et al. (AAPS PharmSciTech, 2022)

Expression patterns and correlation analyses of muscle-specific genes in the process of sheep myoblast differentiation - Hejie Wang; Minmin Dou; Jun Li; Peng Cao; Junling Li; Tianyan Guo; Dipeng Zhao; Ajab Khan; Yingliang Li; Baojun Li; Jian Qin; Rong Du (In Vitro Cellular & Developmental Biology - Animal, 2022)

Heterogeneous Fenton degradation of persistent organic pollutants using natural chalcopyrite: effect of water matrix and catalytic mechanism - Jiapeng Yang; Rong Huang; Yijun Cao; Hui Wang; Andrei Ivanets; Chongqing Wang (Environmental Science and Pollution Research, 2022)

Immobilization of Chitosanase on Magnetic Nanoparticles: Preparation, Characterization and Properties - Yimeng Cheng; Zhaoyue Li; Huihui Sun; Ling Zhao; Zhen Liu; Rong Cao; Qi Liu; Xiangzhao Mao (Journal of Ocean University of China, 2022)

A strategy for establishing an efficient somatic embryo regeneration system in Castanea mollissima Blume - Xiao-wei Li; Zhi-lin Sun; Yue-rong Gao; Jing-yi Ge; Yu-zhen Tian; Bing Liu; Shi-kan Sun; Ke-feng Fang; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Ambient air pollutants increase the risk of immunoglobulin E–mediated allergic diseases: a systematic review and meta-analysis - Hua Wang; Xian-Bao Li; Xiu-Jie Chu; Nv-Wei Cao; Hong Wu; Rong-Gui Huang; Bao-Zhu Li; Dong-Qing Ye (Environmental Science and Pollution Research, 2022)

Observational Analysis of the Formation Reasons and Evolution Law of Winter Counter-Wind Current in Jiazi Sea Area of Northeastern South China Sea - Yizhan Chen; Yonggang Cao; Shizhi Liao; Yuan Ma; Yuqiang Liu; Yongzhong Ouyang; Rong Xiang (Journal of Marine Science and Engineering, 2022)
Based on the observational data of wind, current, and sea surface temperature in the Jiazi sea area of the northeastern South China Sea in 2018 and the satellite remote sensing data of sea surface temperature in the northern South China Sea, this paper explores the formation reasons and evolution law of winter counter-wind currents in the Jiazi sea area of the northeastern South China Sea. The results show that: (1) The counter-wind current in the Jiazi sea occurs only in certain time periods instead of the entire winter; (2) When the eastern component of wind stress weakens, the eastern component of seafloor friction also weakens to some extent. A high-frequency northeast current often occurs in the bottom layer of the sea area, indicating that the formation of winter counter-wind current in the Jiazi sea area is a result of the concerted action of wind stress, the baroclinic effect, and geostrophic effect; (3) When the counter-wind current is formed, there is a low temperature water mass in the northwest of Jiazi and a high-temperature water mass in the southeast. The baroclinic effect causes the sea water to flow to the shore and produce a westward flow on the shore, and northeastward counter-wind current occurs on convergent sea water on the shore due to the baroclinic effect and geostrophic effect (Ekman effect). Therefore, two different current systems are formed in the northeastern South China Sea in winter with 116° E as the boundary. The appearance of cold water masses in the northwest of 116° E sea area and warm water masses in the southeast of the South China Sea is the key to the formation of both the two different current systems with 116° E as the boundary and the winter counter-wind flow; (4) The formation and disappearance of the counter-wind current can be divided into four stages: in the first stage, the northeast monsoon gradually relaxes to become the southeast wind, forming the northwest current; in the second stage, the warm water masses on the west side of the Luzon Strait flow to the coastal waters due to the northwest current, forming a significant onshore pressure gradient force; in the third stage, a high-temperature seawater convergence zone is formed in the Jiazi sea area, forming southwest and northeast pressure gradient forces, and the northwest coastal current forms a counter-wind current under the combined action of pressure gradient force and geostrophic effect; in the fourth stage, the northeast monsoon intensifies and the counter-wind current weakens gradually until it disappears, and the sea water flows to the southwest again.

First report of Botryosphaeria dothidea causing leaf blotch of Mahonia bealei in China - Yi-Jia Cao; Rong-Han Chen; Yuan-Zhi Si; Li-Hua Zhu (Journal of Plant Pathology, 2022)

Urinary phthalate metabolites in pregnant women: occurrences, related factors, and association with maternal hormones - Wei Wu; Zhi-li Ma; Fang Yang; Ping Wu; De-xin Zhang; Rong Zeng; Dan-ling Sun; Liu Cao (Environmental Science and Pollution Research, 2022)

Effective adsorption of zeolite/carbon composite molecular sieve synthesized from spent bleaching earth - Shixiang Zuo; Xiaoman Cao; Wenjie Liu; Tianhua Liu; Xiazhang Li; Chao Yao; Rong Xu; Yongsheng Fu (Environmental Science and Pollution Research, 2022)

Comparison of nominal and standardized catch per unit effort data in quantifying habitat suitability of skipjack tuna in the equatorial Pacific Ocean - Cheng Zhou; Yuanyuan Hu; Jie Cao; Liuxiong Xu; Xuefang Wang; Rong Wan; Yu Xiao; Jiangfeng Zhu; Hao Tang (Acta Oceanologica Sinica, 2022)

Preparation and In Vitro Characterization of Gelatin Methacrylate for Corneal Tissue Engineering - Yayun Yan; Yanyan Cao; Rong Cheng; Zhizhong Shen; Yajing Zhao; Yixia Zhang; Guohong Zhou; Shengbo Sang (Tissue Engineering and Regenerative Medicine, 2022)

Digoxin Ameliorates Glymphatic Transport and Cognitive Impairment in a Mouse Model of Chronic Cerebral Hypoperfusion - Jie Cao; Di Yao; Rong Li; Xuequn Guo; Jiahuan Hao; Minjie Xie; Jia Li; Dengji Pan; Xiang Luo; Zhiyuan Yu; Minghuan Wang; Wei Wang (Neuroscience Bulletin, 2022)

Exercise Ameliorates Fluoride-induced Anxiety- and Depression-like Behavior in Mice: Role of GABA - Qiqi Cao; Jixiang Wang; Yanru Hao; Fangye Zhao; Rong Fu; Yanghuan Yu; Jundong Wang; Ruiyan Niu; Shengtai Bian; Zilong Sun (Biological Trace Element Research, 2022)

Overexpression of IbMPK3 increases low-temperature tolerance in transgenic sweetpotato - Rong Jin; Ho Soo Kim; Tao Yu; Ming Liu; Wenhui Yu; Peng Zhao; Aijun Zhang; Qiangqiang Zhang; Yaju Liu; Qinghe Cao; Sang-Soo Kwak; Zhonghou Tang (Plant Biotechnology Reports, 2022)

The Sources and Burial of Marine Organic Carbon in the Eastern China Marginal Seas - Yali Cao; Rong Bi; Xingchen Wang; Xi Chen; Jingwen Hu; Yaoyao Wang; Yiqing Jiang; Hailong Zhang; Lei Xing; Meixun Zhao (Frontiers in Marine Science, 2022)
The ecological functions and biogeochemical processes of continental marginal seas are important for the global carbon cycle. In the eastern China marginal seas (ECMS), phytoplankton productivity has increased significantly in recent decades, but the sources and burial processes of marine organic carbon (OC) remain under-studied. We analyzed the contents of marine lipid biomarkers (brassicasterol, dinosterol, and C 37 alkenones) in surface suspended particles obtained from seven cruises between 2010 and 2015, and in surface sediments from eight cruises between 2006 and 2012 in the ECMS, to estimate marine OC sources and burial. The correlations between lipid biomarkers and environmental factors were quantified to reveal controlling factors. The study area was divided into four regions according to cluster analysis conducted based on sediment parameters. Our results showed that the concentrations of marine lipid biomarkers in surface water were high near large estuaries such as the Changjiang River Estuary and the Yellow River Estuary, but those in surface sediments were high in mud areas. Nutrient concentration was a key factor controlling phytoplankton biomass in surface water, with high nutrients enhancing the growth of diatoms and dinoflagellates, while haptophytes were more abundant in low-nutrient, high-salinity and cold environments. High marine OC contents calculated from total OC δ 13 C were mainly associated with fine sediments transported by coastal currents, and finally deposited in mud areas. The proto-burial efficiency of marine OC in the ECMS (7–19%) was markedly higher than the mean value in global marginal seas, with high values being located in the western coast of the ECMS. The proto-burial efficiency of total marine lipid biomarkers (6–24%) was quantified for the first time in our study, with overall values and spatial patterns similar to that of marine OC. A key parameter for marine OC and marine biomarker proto-burial efficiency was sediment grain size. The smaller the sediment grain size was, the better the marine OC and marine biomarker were retained. Our study provides an important basis to elucidate spatial distribution patterns and forcing mechanisms of marine OC in surface water (production process) and surface sediments (burial process), and to estimate carbon budgets in large marginal seas.

Biocompatible chitosan/polyethylene glycol/multi-walled carbon nanotube composite scaffolds for neural tissue engineering - Shengbo Sang; Rong Cheng; Yanyan Cao; Yayun Yan; Zhizhong Shen; Yajing Zhao; Yanqing Han (Journal of Zhejiang University-SCIENCE B, 2022)

The combined toxicity and mechanism of multi-walled carbon nanotubes and nano zinc oxide toward the cabbage - Mo Hong; Ji-Lai Gong; Wei-Cheng Cao; Rong Fang; Zhe Cai; Jun Ye; Zeng-Ping Chen; Wang-Wang Tang (Environmental Science and Pollution Research, 2022)

Dietary pectin caused great changes in bile acid profiles of Pelteobagrus fulvidraco - Xiamin Cao; Shengjie Ren; Chunfang Cai; Qin Ni; Xinyue Li; Yunhe Meng; Zijing Meng; Ye Shi; Huangen Chen; Rong Jiang; Ping Wu; Yuantu Ye (Fish Physiology and Biochemistry, 2021)

Predictive value of monocyte to HDL cholesterol ratio for stroke-associated pneumonia in patients with acute ischemic stroke - Yaming Sun; Juan Lu; Danni Zheng; Jufen Qian; Hongxin Zhang; Dong Xing; Fengdan Rong; Yongjun Cao; Chun-Feng Liu; Shoujiang You (Acta Neurologica Belgica, 2021)

3D Localization of Coal Fires Based on Self-Potential Data: Sandbox Experiments - Zhenlu Shao; Rong Deng; Tao Zhou; Fei Cao; Huahai Sun; Long Chen; Yu Yuan; Xiaoxing Zhong (Pure and Applied Geophysics, 2021)

Emerging role of air pollution in chronic kidney disease - Yue Chen; Fan Cao; Jian-Ping Xiao; Xin-Yu Fang; Xue-Rong Wang; Li-Hong Ding; De-Guang Wang; Hai-Feng Pan (Environmental Science and Pollution Research, 2021)

Aquamicrobium zhengzhouense sp. nov., a Bacterium Isolated from Farmland Soil Applied with Amino Acid Fertilizer - Xiang Wang; Chun-Fu Zhou; Jia-Rong Cheng; Sheng-Fei Cao; Hong-Xing Yang; Jian-Rong Zhao (Current Microbiology, 2021)

Mesozoic-Cenozoic Volcanic Cycle and Volcanic Reservoirs in East China - Guangfu Xing; Jianqing Li; Zheng Duan; Mingxuan Cao; Minggang Yu; Pingli Chu; Rong Chen (Journal of Earth Science, 2021)

Surfactant-assisted adsorption of uranyl ions in aqueous solution on TiO2/polythiophene nanocomposite - Youqun Wang; Yinghui Xie; Zhiyang Zheng; Dejun Zeng; Ying Dai; Zhibin Zhang; Xiaohong Cao; Rong Zou; Yunhai Liu (Environmental Science and Pollution Research, 2021)

Complete nucleotide sequence of a new carlavirus infecting Aconitum carmichaelii in China - Rong Wang; Bingwei Chen; Yong Li; Mengji Cao; Wanlong Ding (Archives of Virology, 2021)

Variation in rare earth element (REE), aluminium (Al) and silicon (Si) accumulation among populations of the hyperaccumulator Dicranopteris linearis in southern China - Wen-Shen Liu; Hong-Xiang Zheng; Chang Liu; Mei-Na Guo; Shi-Chen Zhu; Yue Cao; Rong-Liang Qiu; Jean Louis Morel; Antony van der Ent; Ye-Tao Tang (Plant and Soil, 2021)

Clinical and microbiological characteristics of adults with hospital-acquired pneumonia: a 10-year prospective observational study in China - Yuyao Yin; Chunjiang Zhao; Henan Li; Longyang Jin; Qi Wang; Ruobing Wang; Yawei Zhang; Jiangang Zhang; Hui Wang; Chunxia Yang; Bin Cao; Yingmei Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Increased depression risk for elderly women with high blood levels of strontium and barium - Jia Lv; Yan-ling Li; Wen-qiang Ren; Rong Li; Jian-rong Chen; Chao Bao; Zhi-ping Du; Shun Feng; Ling Gu; Hui Gao; Kai-yong Liu; Lin-sheng Yang; et al. (Environmental Chemistry Letters, 2021)

Curcumin protects thymus against D-galactose-induced senescence in mice - Jie-han Li; Ting-ting Wei; Li Guo; Jia-hui Cao; Yuan-kang Feng; Shu-ning Guo; Guo-hong Liu; Yi Ding; Yu-rong Chai (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Establishment and optimization of a high-throughput mimic perfusion model in ambr® 15 - Lu Jin; Zhen-Shou Wang; Yun Cao; Rui-Qiang Sun; Hang Zhou; Rong-Yue Cao (Biotechnology Letters, 2021)

Flavor Characteristics of Different Crops of Laver (Porphyra yezoensis) During One Harvest Cycle - Rong Cao; Mengyue Hu; Ling Zhao; Lianzhu Wang; Qi Liu (Journal of Ocean University of China, 2021)

Spatial variability of bigeye tuna habitat in the Pacific Ocean: Hindcast from a refined ecological niche model - Cheng Zhou; Rong Wan; Jie Cao; Liuxiong Xu; Xuefang Wang; Jiangfeng Zhu (Fisheries Oceanography, 2021)
Habitat distribution is critically informative for stock assessment, since incorporating its variabilities can have important implications for the estimation of stock biomass or the relative abundance index. A refined ecological niche model with habitat characteristic parameterization was developed to reconstitute a 3‐D ecological map of bigeye tuna in the Pacific Ocean. We determined the boundaries and hierarchies of oceanographic features and hydrological conditions at horizontal and vertical scales to define the habitat preference of bigeye tuna associated with their feeding and physiological requirements. Ecogeographic projections underlined the depth‐ and region‐specific habitat distribution of bigeye tuna, with noticeable dynamic variations in the response to climate variability. Depths from 300 to 400 m represented layers of the most productive habitat, which was widespread through the equatorial Pacific Ocean and extended to the north‐central Pacific Ocean. The proportion of high‐quality habitat size in the north Pacific had a strictly regular intra‐annual cycle with peaks during the winter. Climate variability appeared to disturb the balance of the regular fluctuations in habitat size in the equatorial Pacific. Habitat hotspots during an El Niño period were characterized by their expansion to the north of the Hawaiian islands, shrinkage in the west for the hotspot band north of the Equator, and an eastern shift for the band south of the Equator. This variability may be the consequence of the incorporated fluctuations of the oxygen minimum zones (OMZ), current systems, and stratification in the open ocean.

The Joubert Syndrome Gene arl13b is Critical for Early Cerebellar Development in Zebrafish - Jian Zhu; Han-Tsing Wang; Yu-Rong Chen; Ling-Ya Yan; Ying-Ying Han; Ling-Yan Liu; Ying Cao; Zhi-Zhi Liu; Hong A. Xu (Neuroscience Bulletin, 2020)
Joubert syndrome is characterized by unique malformation of the cerebellar vermis. More than thirty Joubert syndrome genes have been identified, including ARL13B . However, its role in cerebellar development remains unexplored. We found that knockdown or knockout of arl13b impaired balance and locomotion in zebrafish larvae. Granule cells were selectively reduced in the corpus cerebelli, a structure homologous to the mammalian vermis. Purkinje cell progenitors were also selectively disturbed dorsomedially. The expression of atoh1 and ptf1 , proneural genes of granule and Purkinje cells, respectively, were selectively down-regulated along the dorsal midline of the cerebellum. Moreover, wnt1 , which is transiently expressed early in cerebellar development, was selectively reduced. Intriguingly, activating Wnt signaling partially rescued the granule cell defects in arl13b mutants. These findings suggested that Arl13b is necessary for the early development of cerebellar granule and Purkinje cells. The arl13b -deficient zebrafish can serve as a model organism for studying Joubert syndrome.

A Review of Co3O4-based Catalysts for Formaldehyde Oxidation at Low Temperature: Effect Parameters and Reaction Mechanism - Rong Li; Yu Huang; Dandan Zhu; Wingkei Ho; Shuncheng Lee; Junji Cao (Aerosol Science and Engineering, 2020)

Isolation and Identification of Endophytic Fungi in Kernels of Coix lachrymal-jobi L. Cultivars - Guan-rong Li; Bao-hong Cao; Wei Liu; Rui-hua Ren; Jie Feng; Da-jin Lv (Current Microbiology, 2020)

Fluoride-Induced Alteration in the Diversity and Composition of Bacterial Microbiota in Mice Colon - Rong Fu; Ruiyan Niu; Rui Li; Baijuan Yue; Xuhua Zhang; Qiqi Cao; Jundong Wang; Zilong Sun (Biological Trace Element Research, 2020)

GaHD1, a candidate gene for the Gossypium arboreum SMA-4 mutant, promotes trichome and fiber initiation by cellular H2O2 and Ca2+ signals - Mingquan Ding; Yuefen Cao; Shae He; Jian Sun; Huaqin Dai; Hua Zhang; Chendong Sun; Yurong Jiang; Andrew H. Paterson; Junkang Rong (Plant Molecular Biology, 2020)

Characterization of Pingliang xiaoheidou (ZDD 11047), a soybean variety with resistance to soybean cyst nematode Heterodera glycines - Wei Guo; Jing S. Chen; Feng Zhang; Ze Y. Li; Hai F. Chen; Chan J. Zhang; Li M. Chen; Song L. Yuan; Rong Li; Dong Cao; Qing N. Hao; Shui L. Chen; et al. (Plant Molecular Biology, 2020)

Microbiota and Shelf Life of Whole and Gutted Pacific Saury (Cololabis saira) During Refrigerated Storage - Rong Cao; Ruihuan Lin; Huihui Sun; Qi Liu (Journal of Ocean University of China, 2020)

Atorvastatin ameliorates depressive behaviors and neuroinflammatory in streptozotocin-induced diabetic mice - Zhang Hai-Na; Yu Xu-Ben; Tang Cong-Rong; Cao Yan-Cheng; Yang Fan; Xu Lei-Mei; Sun Ruo-Lan; Ye-Zi; Wang Ye-Xuan; Liang Jing (Psychopharmacology, 2020)

Genome-wide identification, characterisation and expression profile analysis of DEAD-box family genes in sweet potato wild ancestor Ipomoea trifida under abiotic stresses - Rong Wan; Jingran Liu; Zhengmei Yang; Panpan Zhu; Qinghe Cao; Tao Xu (Genes & Genomics, 2020)

Development of Climate and Earth System Models in China: Past Achievements and New CMIP6 Results - Tianjun Zhou; Ziming Chen; Liwei Zou; Xiaolong Chen; Yongqiang Yu; Bin Wang; Qing Bao; Ying Bao; Jian Cao; Bian He; Shuai Hu; Lijuan Li; et al. (Journal of Meteorological Research, 2020)

Relationships amongst sex ratio of progeny in Anastatus disparis (Hymenoptera: Eupelmidae), sperm depletion and decreased fecundity - Peng-Cheng Liu; Hai-Xiang Wei; Dan-Dan Cao; Jian-Rong Wei (Applied Entomology and Zoology, 2020)

Agrobacterium-mediated genetic transformation of Chinese chestnut (Castanea mollissima Blume) - Zhi-lin Sun; Xiao Li; Wan Zhou; Jun-di Yan; Yue-rong Gao; Xiao-wei Li; Jia-chen Sun; Ke-feng Fang; Qing Zhang; Yu Xing; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)
Chinese chestnut ( Castanea mollissima ) is an important germplasm resource for the breeding of Castanea species worldwide with vital ecological and economic value. Biotechnology overcomes the limitations of traditional breeding and accelerates germplasm improvement. However, a genetic transformation system for Chinese chestnut has not yet been established. In this study, a stable and efficient Agrobacterium -mediated genetic transformation method for Chinese chestnut is described. Embryogenic calli of C. mollissima cv. ‘Yanshanhongli’ were used as the target material. The sensitivity of embryogenic calli to kanamycin was determined, whereby the proliferation of non-transformed calli was completely inhibited at 180 mg/L. Antibiotic inhibition results for Chinese chestnut embryogenic calli showed that 50 mg/L cefotaxime and 500 μM timentin completely inhibited the growth of Agrobacterium tumefaciens but did not affect the normal growth of Chinese chestnut embryogenic calli. When embryogenic calli were co-cultured for 2 days with Agrobacterium tumefaciens strain AGL1 harboring the PBI121-EGFP plasmid, an embryogenic callus transformation efficiency of 4.55% was obtained, and two transgenic chimera were acquired. This Agrobacterium -mediated transformation system for Chinese chestnut provides a fundamental platform for genetic improvement of core germplasm and for further verification of gene function.

Preferential insertion of a Ty1 LTR-retrotransposon into the A sub-genome’s HD1 gene significantly correlated with the reduction in stem trichomes of tetraploid cotton - Mengling Tang; Xingcheng Wu; Yuefen Cao; Yuan Qin; Mingquan Ding; Yurong Jiang; Chengdong Sun; Hua Zhang; Andrew H. Paterson; Junkang Rong (Molecular Genetics and Genomics, 2020)

RETRACTED ARTICLE: Emerging protective roles of shengmai injection in septic cardiomyopathy in mice by inducing myocardial mitochondrial autophagy via caspase-3/Beclin-1 axis - Yan Cao; Xiaotong Han; Hongwei Pan; Yu Jiang; Xiang Peng; Weiwei Xiao; Jingjing Rong; Fang Chen; Jin He; Lianhong Zou; Yi Tang; Yanfang Pei; et al. (Inflammation Research, 2020)

Combined gastroscopic and choledochoscopic transabdominal nasobiliary drainage - Song-mei Lou; Min Zhang; Zheng-rong Wu; Gui-xing Jiang; Hua Shen; Yi Dai; Yue-long Liang; Li-ping Cao; Guo-ping Ding (Journal of Zhejiang University-SCIENCE B, 2019)

MiR-1261/circ-PTPRZ1/PAK1 pathway regulates glioma cell growth and invasion - Feng Zhang; Shu-rong Mai; Fei-peng Cao; Can-xian Cao; Liang Zhang (Human Cell, 2019)

Nitrogen use-inefficient oilseed rape genotypes exhibit stronger growth potency during the vegetative growth stage - Xiao Guo; Huiying He; Rong An; Yuying Zhang; Rui Yang; Lanqin Cao; Xiaoming Wu; Biyun Chen; Hui Tian; Yajun Gao (Acta Physiologiae Plantarum, 2019)

Fluorescence “Off-On” Probe for L-Cysteine Detection Based on Nitrogen Doped Carbon Dots - Yin-long Xu; Rong-biao Bai; Cai-yu Qi; Zeng Ren; Xiu-zhi Jia; Zi-gui Kan; Cao-long Li; Fei Wang (Journal of Fluorescence, 2019)

Effects of different substrates on nitrogen and phosphorus removal in horizontal subsurface flow constructed wetlands - Rui Xu; Yong Zhang; Rong Liu; Yun Cao; Guoxiang Wang; Lingchen Ji; Yifan Xu (Environmental Science and Pollution Research, 2019)

Calcium intake and colon cancer risk subtypes by tumor molecular characteristics - NaNa Keum; Li Liu; Tsuyoshi Hamada; Zhi Rong Qian; Jonathan A. Nowak; Yin Cao; Annacarolina da Silva; Keisuke Kosumi; Mingyang Song; Daniel Nevo; Molin Wang; Andrew T. Chan; et al. (Cancer Causes & Control, 2019)

In Vitro Susceptibility of Berberine Combined with Antifungal Agents Against the Yeast Form of Talaromyces marneffei - Hong Luo; Kai-su Pan; Xiao-lu Luo; Dong-yan Zheng; Alex Andrianopoulos; Le-min Wen; Yan-qing Zheng; Jing Guo; Chun-yang Huang; Xiu-ying Li; Rong Hu; Yu-jiao Li; et al. (Mycopathologia, 2019)

Geochronology and Geochemistry of the Granites from the Longtoushan Hydrothermal Gold Deposit in the Dayaoshan Area, Guangxi: Implication for Petrogenesis and Mineralization - Lihua Qian; Jianqing Lai; Lifang Hu; Rong Cao; Shilong Tao; Bei You (Journal of Earth Science, 2019)

Chemical and boron isotopic compositions of tourmaline in the Longtoushan hydrothermal gold deposit, Guangxi, China: implications for gold mineralization - Lihua Qian; Jianqing Lai; Shugen Zhang; Lifang Hu; Rong Cao; Shilong Tao (Acta Geochimica, 2019)

Loop-mediated isothermal amplification (LAMP) detection of Phytophthora hibernalis, P. syringae and P. cambivora - Guan-Rong Li; Guo-Ming Huang; Lin-Hui Zhu; Dajin Lv; Baohong Cao; Fang Liao; Jia-Feng Luo (Journal of Plant Pathology, 2019)

A new actinomycin Z analogue with an additional oxygen bridge between chromophore and β -depsipentapeptide from Streptomyces sp. KIB-H714 - Miao Dong; Pei Cao; Ya-Tuan Ma; Jianying Luo; Yijun Yan; Rong-Tao Li; Sheng-Xiong Huang (Natural Product Research, 2019)

The Role of miR-150 in Stress-Induced Anxiety-Like Behavior in Mice - Wen-Juan Zhang; Wen-Yu Cao; Yan-Qing Huang; Yan-Hui Cui; Bo-Xuan Tu; Lai-Fa Wang; Guang-Jing Zou; Yu Liu; Zhao-Lan Hu; Rong Hu; Chang-Qi Li; Xiao-Wei Xing; et al. (Neurotoxicity Research, 2019)

Comparative Study on Antineoplastic Activity of Polysaccharide from Four Kinds of Sea Cucumber - Ling Zhao; Qi Liu; Xianqing Yang; Rong Cao (Journal of Ocean University of China, 2018)

Co-targeting PLK1 and mTOR induces synergistic inhibitory effects against esophageal squamous cell carcinoma - Ting-Ting Liu; Kai-Xia Yang; Jing Yu; Ying-Ya Cao; Jian-Song Ren; Jia-Jie Hao; Bei-Qing Pan; Sai Ma; Li-Yan Yang; Yan Cai; Ming-Rong Wang; Yu Zhang (Journal of Molecular Medicine, 2018)

Diagnosis of Wetland Ecosystem Health in the Zoige Wetland, Sichuan of China - Chunying Wu; Wei Chen; Chunxiang Cao; Rong Tian; Di Liu; Daming Bao (Wetlands, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Triplex real-time PCR detection of three quarantine Phytophthora pathogens infecting Malus Miller - Fang Liao; Ying Zhang; Lin-Hui Zhu; Baohong Cao; Dajin Lv; Jia-Feng Luo; Guan-Rong Li (Journal of Plant Diseases and Protection, 2018)

Studies of the Interaction of Influenza Virus RNA Polymerase PAN with Endonuclease Inhibitors - Li-hua Dong; Xiao-rong Cao (Interdisciplinary Sciences: Computational Life Sciences, 2018)

De novo transcriptome analysis of an albino mutant Pasphiopedilum pacific shamrock reveals reduced expression of genes related to chloroplast biosynthesis and division - Han Li; Hua Cao; Rong-pei Yu; Zhen Miao; Ji-hua Wang; Su-Ping Qu; Qiang Yuan; Shen-chong Li (Horticulture, Environment, and Biotechnology, 2018)

Mixed Cadzow filtering method in fractional Fourier domain - Zhong-Lin Cao; Jun-Xing Cao; Fu-Rong Wu; Guang-Ming He; Qiang Zhou; Yu-Lin Wu (Applied Geophysics, 2018)

Up-regulation of contractile endothelin receptors by airborne fine particulate matter in rat mesenteric arteries via activation of MAPK pathway - Rong Wang; Lei Cao; Zhenxing Shen; Yongxiao Cao (Environmental Science and Pollution Research, 2018)

Study on the influential biochemical indices of Cd(II) on Eisenia fetida in oxidative stress by principal component analysis in the natural soil - Yucui Ning; Liyan Liu; Guohua Rong; Xu Cao; Jing Li; Ye Su; Dongxing Zhou (Environmental Science and Pollution Research, 2018)

Protodioscin ameliorates oxidative stress, inflammation and histology outcome in Complete Freund’s adjuvant induced arthritis rats - Jia-Yu Liu; Ya-Ling Hou; Rong Cao; Hong Xia Qiu; Guo-Hua Cheng; Ran Tu; Li Wang; Jun-Li Zhang; Dan Liu (Apoptosis, 2017)

Nortirucallane A, a new tirucallane-type nortriterpenoid isolated from Lonicerae japonicae flos - Xu Wang; Jing Zhang; Ya-qun Li; Bao-xiang Du; Qi-hui Sun; Yun-jiao Cao; Hai-qiang Jiang; Yu-hong Liu; Hong-lei Zhou; Rong Rong (Natural Product Research, 2017)

Normobaric Hyperoxia Extends Neuro- and Vaso-Protection of N-Acetylcysteine in Transient Focal Ischemia - Yushan Liu; Wen-Cao Liu; Yanyun Sun; Xianzhi Shen; Xiaona Wang; Hui Shu; Rong Pan; Chun-Feng Liu; Wenlan Liu; Ke Jian Liu; Xinchun Jin (Molecular Neurobiology, 2017)

Transient Receptor Potential-canonical 1 is Essential for Environmental Enrichment-Induced Cognitive Enhancement and Neurogenesis - Lai-Ling Du; Lin Wang; Xi-Fei Yang; Ping Wang; Xiao-Hong Li; Da-Min Chai; Bing-Jin Liu; Yun Cao; Wei-Qi Xu; Rong Liu; Qing Tian; Jian-Zhi Wang; et al. (Molecular Neurobiology, 2017)

High pressure treatment changes spoilage characteristics and shelf life of Pacific oysters (Crassostrea gigas) during refrigerated storage - Rong Cao; Ling Zhao; Qi Liu (Journal of Ocean University of China, 2017)

Proceedings of the third international molecular pathological epidemiology (MPE) meeting - Peter T. Campbell; Timothy R. Rebbeck; Reiko Nishihara; Andrew H. Beck; Colin B. Begg; Alexei A. Bogdanov; Yin Cao; Helen G. Coleman; Gordon J. Freeman; Yujing J. Heng; Curtis Huttenhower; Rafael A. Irizarry; et al. (Cancer Causes & Control, 2017)

U–Pb dating of zircon and cassiterite from the Early Cretaceous Jiaojiguan iron-tin polymetallic deposit, implications for magmatism and metallogeny of the Tengchong area, western Yunnan, China - Hua-Wen Cao; Yun-Hui Zhang; Qiu-Ming Pei; Rong-Qing Zhang; Li Tang; Bin Lin; Guo-Jun Cai (International Geology Review, 2017)

Genome-wide analysis of Gro/Tup1 family corepressors and their responses to hormones and abiotic stresses in maize - Hongyou Li; Kaifeng Huang; Hanmei Du; Hongling Wang; Xin Chen; Shibin Gao; Hailan Liu; Moju Cao; Yanli Lu; Tingzhao Rong; Suzhi Zhang (Journal of Plant Biology, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Chryseobacterium chengduensis sp. nov. isolated from the air of captive giant panda enclosures in Chengdu, China - Cai-fang Wen; Li-xin Xi; Shan Zhao; Zhong-xiang Hao; Lu Luo; Hong Liao; Zhen-rong Chen; Rong She; Guo-quan Han; San-jie Cao; Rui Wu; Qi-gui Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2016)

Increasing the immune activity of exosomes: the effect of miRNA-depleted exosome proteins on activating dendritic cell/cytokine-induced killer cells against pancreatic cancer - Ri-sheng Que; Cheng Lin; Guo-ping Ding; Zheng-rong Wu; Li-ping Cao (Journal of Zhejiang University-SCIENCE B, 2016)

Valproic Acid Influences MTNR1A Intracellular Trafficking and Signaling in a β-Arrestin 2-Dependent Manner - Ling-juan Hong; Quan Jiang; Sen Long; Huan Wang; Ling-di Zhang; Yun Tian; Cheng-kun Wang; Jing-jing Cao; Rong-rong Tao; Ji-yun Huang; Mei-hua Liao; Ying-mei Lu; et al. (Molecular Neurobiology, 2016)

MiR-219 Protects Against Seizure in the Kainic Acid Model of Epilepsy - Honghua Zheng; Rong Tang; Yi Yao; Zhilin Ji; Yuanyuan Cao; Zhaoji Liu; Feng Peng; Wenjie Wang; Dan Can; Huiqin Xing; Guojun Bu; Huaxi Xu; et al. (Molecular Neurobiology, 2016)

DNA methylation analysis of sterile and fertile CMS-C hybrids and their parents in maize - Bo Chen; Yan Zhang; Yanli Lu; Jing Wang; Suzhi Zhang; Hai Lan; Tingzhao Rong; Moju Cao (Journal of Plant Biochemistry and Biotechnology, 2016)

Lysobacter chengduensis sp. nov. Isolated from the Air of Captive Ailuropoda melanoleuca Enclosures in Chengdu, China - Caifang Wen; Lixin Xi; Rong She; Shan Zhao; Zhongxiang Hao; Lu Luo; Hong Liao; Zhenrong Chen; Guoquan Han; Sanjie Cao; Rui Wu; Qigui Yan; et al. (Current Microbiology, 2016)

Genetic fine mapping and candidate gene analysis of the Gossypium hirsutum Ligon lintless-1 (Li1) mutant on chromosome 22(D) - Yurong Jiang; Mingquan Ding; Yuefen Cao; Fen Yang; Hua Zhang; Shae He; Huaqin Dai; Huanfeng Hao; Junkang Rong (Molecular Genetics and Genomics, 2015)

The involvement of c-Myc in the DNA double-strand break repair via regulating radiation-induced phosphorylation of ATM and DNA-PKcs activity - Fengmei Cui; Rong Fan; Qiu Chen; Yongming He; Man Song; Zengfu Shang; Shimeng Zhang; Wei Zhu; Jianping Cao; Hua Guan; Ping-Kun Zhou (Molecular and Cellular Biochemistry, 2015)

Application of Lactic Acid Bacteria (LAB) in freshness keeping of tilapia fillets as sashimi - Rong Cao; Qi Liu; Shengjun Chen; Xianqing Yang; Laihao Li (Journal of Ocean University of China, 2015)

Molecular characterization of a transcriptionally active Ty1/copia-like retrotransposon in Gossypium - Yuefen Cao; Yurong Jiang; Mingquan Ding; Shae He; Hua Zhang; Lifeng Lin; Junkang Rong (Plant Cell Reports, 2015)

Protective effect of adiponectin on paraquat-induced pulmonary fibrosis in mice - Rong Yao; Yarong He; Zhi Zeng; Zongan Liang; Yu Cao (Molecular & Cellular Toxicology, 2015)

The improvement of a regional climate model by coupling a land surface model with eco-physiological processes: A case study in 1998 - Li Dan; Fuqiang Cao; Rong Gao (Climatic Change, 2015)

Genome-wide investigation and transcriptome analysis of the WRKY gene family in Gossypium - Mingquan Ding; Jiadong Chen; Yurong Jiang; Lifeng Lin; YueFen Cao; Minhua Wang; Yuting Zhang; Junkang Rong; Wuwei Ye (Molecular Genetics and Genomics, 2015)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Applying support vector regression analysis on grip force level-related corticomuscular coherence - Yao Rong; Xixuan Han; Dongmei Hao; Liu Cao; Qing Wang; Mingai Li; Lijuan Duan; Yanjun Zeng (Journal of Computational Neuroscience, 2014)

Knockdown of LYRM1 Rescues Insulin Resistance and Mitochondrial Dysfunction Induced by FCCP in 3T3-L1 Adipocytes - Min Zhang; Zhen-Ying Qin; Yong-mei Dai; Yu-Mei Wang; Guan-zhong Zhu; Ya-Ping Zhao; Chen-Bo Ji; Jin-Gai Zhu; Chun-Mei Shi; Jie Qiu; Xin-Guo Cao; Xi-Rong Guo (Cell Biochemistry and Biophysics, 2014)

Diallyl disulfide inhibits proliferation and transdifferentiation of lung fibroblasts through induction of cyclooxygenase and synthesis of prostaglandin E2 - Yanhua Wang; Rong Cao; Bo Wei; Xiaoyu Chai; Dan Sun; Y. Guan; Xin-min Liu (Molecular and Cellular Biochemistry, 2014)

Streptomycin inhibits electrophysiological changes induced by stretching of chronically infarcted rat hearts - Jun-xian Cao; Lu Fu; Qian-ping Gao; Rong-sheng Xie; Fan Qu (Journal of Zhejiang University-SCIENCE B, 2014)

The rare intracellular RET mutation p.S891A in a Chinese Han family with familial medullary thyroid carcinoma - Xiao-Ping Qi; Rong-Xin Zhang; Jin-Lin Cao; Zhen-Guang Chen; Hang-Yang Jin; Ren-Rong Yang (Journal of Biosciences, 2014)

Large-scale screening maize germplasm for low-phosphorus tolerance using multiple selection criteria - Li-tian Zhang; Jia Li; Ting-zhao Rong; Shi-bin Gao; Feng-kai Wu; Jie Xu; Meng-lu Li; Mo-ju Cao; Jing Wang; Er-liang Hu; Ya-xi Liu; Yan-li Lu (Euphytica, 2014)

Interval Q inversion based on zero-offset VSP data and applications - Gu-Lan Zhang; Xi-Ming Wang; Zhen-Hua He; Jun-Xing Cao; Ke-En Li; Jiao-Jun Rong (Applied Geophysics, 2014)

Eudragit L/HPMCAS Blend Enteric-Coated Lansoprazole Pellets: Enhanced Drug Stability and Oral Bioavailability - Yu Fang; Guozheng Wang; Rong Zhang; Zhihua Liu; Zhenghua Liu; Xiaohui Wu; Deying Cao (AAPS PharmSciTech, 2014)

Genomic comparison of Salmonella typhimurium DT104 with non-DT104 strains - Er-Ying Zhao; Hong-Xia Bao; Le Tang; Qing-Hua Zou; Wei-Qiao Liu; Da-Ling Zhu; Jessica Chin; Ying-Ying Dong; Yong-Guo Li; Feng-Lin Cao; Cornelis Poppe; Kenneth E. Sanderson; et al. (Molecular Genetics and Genomics, 2013)

Genetic structure and association mapping of cold tolerance in improved japonica rice germplasm at the booting stage - Di Cui; Chang-ying Xu; Cui-feng Tang; Chun-gang Yang; Teng-qiong Yu; Xin-xiang A; Gui-lan Cao; Fu-rong Xu; Jun-guo Zhang; Long-zhi Han (Euphytica, 2013)

Nonsense-mediated mRNA degradation of CtFAD2-1 and development of a perfect molecular marker for olol mutation in high oleic safflower (Carthamus tinctorius L.) - Qing Liu; Shijiang Cao; Xue-Rong Zhou; Craig Wood; Allan Green; Surinder Singh (Theoretical and Applied Genetics, 2013)

Transjugular intrahepatic portosystemic shunt induced short- and long-term cerebral blood flow variations in cirrhotic patients: an arterial spin labeling MRI study - Gang Zheng; Long Jiang Zhang; Yue Cao; Zhiying Pan; Rong Feng Qi; Ling Ni; Donghong Shi; Xinxin Fan; Guang Ming Lu (Metabolic Brain Disease, 2013)

Purification of antimicrobial peptide from Antarctic Krill (Euphausia superba) and its function mechanism - Ling Zhao; Bangzhong Yin; Qi Liu; Rong Cao (Journal of Ocean University of China, 2013)

Halomonas socia sp. nov., isolated from high salt culture of Dunaliella salina - Jiao Cao; Huai-Yuan Ma; Hai-Yu Li; Kui-Rong Wang; Kun Ruan; Lin-Han Bai (Extremophiles, 2013)

Evaluation of Burma Reed as Substrate for Production of Pleurotus eryngii - Xian-lu Zeng; Jun-fang Lin; Li-qiong Guo; Rong-wei Cao; Wei-qiang Zeng (Indian Journal of Microbiology, 2013)

Musca Domestica Larva Lectin Induces Apoptosis in BEL-7402 Cells Through a Ca2+/JNK-mediated Mitochondrial Pathway - Chun-Ling Wang; Yan Xia; Jian-Zeng Nie; Minghui Zhou; Rong-Ping Zhang; Li-Li Niu; Li-Hua Hou; Xiao-Hong Cao (Cell Biochemistry and Biophysics, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

A fully automatic registration approach based on contour and SIFT for HJ-1 images - XiLiang Ni; ChunXiang Cao; Lin Ding; Tao Jiang; Hao Zhang; HuiCong Jia; GuangHe Li; Jian Zhao; Wei Chen; Wei Ji; Min Xu; MengXu Gao; et al. (Science China Earth Sciences, 2012)

Expression characterization of genes for CMS-C in maize - Ling Huang; Jie Xiang; Jiazhou Liu; Tingzhao Rong; Jing Wang; Yanli Lu; Qilin Tang; Wen Wen; Moju Cao (Protoplasma, 2012)

Relationships between hemorrhage, angioarchitectural factors and collagen of arteriovenous malformations - Hongchuan Niu; Yong Cao; Xuejiang Wang; Xiaowei Xue; Lanbing Yu; Ming Yang; Rong Wang (Neuroscience Bulletin, 2012)

Identification and molecular cytology analysis of cold tolerance introgression lines derived from Oryza sativa L. mating with O. rufipogon Griff. - Xiang-Dong Luo; Liang-Fang Dai; Juan-Fang Cao; Shui-Rong Jian; Ya-Ling Chen; Biao-Lin Hu; Jian-Kun Xie (Euphytica, 2012)

Domestication and geographic origin of O ryza sativa in C hina: insights from multilocus analysis of nucleotide variation of O . sativa and O . rufipogon - Xin Wei; Wei‐Hua Qiao; You‐Tao Chen; Rong‐Sheng Wang; Li‐Rong Cao; Wan‐Xia Zhang; Nan‐Nan Yuan; Zi‐Chao Li; Han‐Lai Zeng; Qing‐Wen Yang (Molecular Ecology, 2012)
Previous studies have indicated that C hina is one of the domestication centres of A sian cultivated rice ( O ryza sativa ), and common wild rice ( O . rufipogon ) is the progenitor of O . sativa . However, the number of domestication times and the geographic origin of A sian cultivated rice in C hina are still under debate. In this study, 100 accessions of A sian cultivated rice and 111 accessions of common wild rice in C hina were selected to examine the relationship between O . sativa and O . rufipogon and thereby infer the domestication and evolution of O . sativa in C hina through sequence analyses of six gene regions, trn C ‐ycf6 in chloroplast genomes, cox3 in mitochondrial genomes and ITS , E hd1 , W axy , H d1 in nuclear genomes. The results indicated that the two subspecies of O . sativa (indica and japonica) were domesticated independently from different populations of O . rufipogon with gene flow occurring later from japonica to indica; S outhern C hina was the genetic diversity centre of O . rufipogon , and the P earl R iver basin near the T ropic of C ancer was the domestication centre of O . sativa in C hina.

Chitosan extends the shelf-life of filleted tilapia (Oreochromis niloticus) during refrigerated storage - Rong Cao; Qi Liu; Bangzhong Yin; Biao Wu (Journal of Ocean University of China, 2012)

Seismic performance of cable-sliding friction bearing system for isolated bridges - Wancheng Yuan; Binbin Wang; Pakchiu Cheung; Xinjian Cao; Zhaojun Rong (Earthquake Engineering and Engineering Vibration, 2012)

Molecular cloning and functional characterization of a novel apple MdCIPK6L gene reveals its involvement in multiple abiotic stress tolerance in transgenic plants - Rong-Kai Wang; Ling-Li Li; Zhong-Hui Cao; Qiang Zhao; Ming Li; Ling-Yun Zhang; Yu-Jin Hao (Plant Molecular Biology, 2012)

Spermidine affects the transcriptome responses to high temperature stress in ripening tomato fruit - Lin Cheng; Rong-rong Sun; Fei-yan Wang; Zhen Peng; Fu-ling Kong; Jian Wu; Jia-shu Cao; Gang Lu (Journal of Zhejiang University-SCIENCE B, 2012)

Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Interleukin-23 as a potential therapeutic target for rheumatoid arthritis - Chao Rong; Wei Hu; Fan-rong Wu; Xiao-juan Cao; Fei-hu Chen (Molecular and Cellular Biochemistry, 2012)

Erratum to: Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Phylogenic analysis of Chinese Leishmania isolates based on small subunit ribosomal RNA (SSU rRNA) and 7 spliced leader RNA (7SL RNA) - Wang Guan; De-Ping Cao; Ke sun; Jia-nan Xu; Jun-rong Zhang; Da-Li Chen; Jian-Ping Chen (Acta Parasitologica, 2012)
The leishmaniases are zoonotic diseases caused by protozoan parasites of the genus Leishmania. Leishmaniases are still endemic in China, especially in the west and northwest froniter regions. To revalue the preliminary phylogenetic results of Chinese Leishmania isolates, we amplified partial fragment of small subunit ribosomal RNA (SSU rRNA) and 7 spliced leader RNA (7SL RNA), then tested the phylogenetic relationships among Chinese Leishmania isolates and their relatives by analyzing SSU rRNA gene sequences and 7SL RNA gene sequences. 19 SSU RNA sequences and 9 7SL RNA sequences were obtained in our study, then analyzed with 42 SSU RNA sequences and 32 7SL RNA sequences retrieved from Genbank, respectively. In the Bayesian analysis of the SSU RNA gene, the isolate MHOM/CN/93/GS7 and the isolate IPHL/CN/77/XJ771 are members of Leishmania donovani complex, while the isolate MHOM/CN/84/JS1 clustered with Leishmania tropica. The other 11 Chinese Leishmania isolates (MHOM/CN/90/WC, MCAN/CN/90/SC11, MHOM/CN/80/XJ801, MHOM/CN/85/GS4, MHOM/CN/84/SD1, MCAN/CN/86/SC7, MHOM/CN/54/#3, MHOM/CN/83/GS2, MHOM/CN/90/SC10H2, MHOM/CN/89/GS6 and MHOM/CN/ 89/GS5) form an unclassified group, defined as Leishmania sp., and the most relative species to this group is L. tarentolae. In the Bayesian analysis of the 7SL RNA gene, 9 Chinese Leishmania isolates also formed an unclassified group with L. tarentolae, including canine isolate 10, MHOM/CN/85/GS4, MHOM/CN/84/SD1, MCAN/CN/86/SC7, MHOM/CN/54/#3, MHOM/ CN/83/GS2, MHOM/CN/90/SC10H2, MHOM/CN/89/GS6 and MHOM/CN/89/GS5. We concluded that: (1) Chinese Leishmania isolates are non-monophyly group; (2) an unclassified group may exist in China, and the most relative species to this group is L. tarentolae; (3) MHOM/CN/84/JS1, which was previously assigned as L. donovani, was most genetically related to L. tropica strain MHOM/SU/74/K27.

Tongxinluo promotes mesenchymal stem cell tube formation in vitro - Xin-yang Hu; Wen-xia Wang; Min-jia Yu; Xian-bao Liu; Rong-rong Wu; Feng Gao; Xin Huang; Jiang Cao; Xiao-jie Xie; Jian-an Wang (Journal of Zhejiang University-SCIENCE B, 2011)

Genistein alters caffeine exposure in healthy female volunteers - Yao Chen; Chang-Qiong Xiao; Yi-Jing He; Bi-Lian Chen; Guo Wang; Gan Zhou; Wei Zhang; Zhi-Rong Tan; Shan Cao; Li-Ping Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2011)

Cytoplasmic male sterility-regulated novel microRNAs from maize - Yaou Shen; Zhiming Zhang; Haijian Lin; Hailan Liu; Jie Chen; Hua Peng; Moju Cao; Tingzhao Rong; Guangtang Pan (Functional & Integrative Genomics, 2011)

Methylobacterium soli sp. nov. a methanol-utilizing bacterium isolated from the forest soil - Yan-Ru Cao; Qian Wang; Rong-Xian Jin; Shu-Kun Tang; Yi Jiang; Wen-Xiang He; Hang-Xian Lai; Li-Hua Xu; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2011)

Accumulation and remobilization of metals in superficial sediments in Tianjin, China - Guang Hong Wu; Shan Shan Cao; Shui Rong Chen; Fang Ting Cao (Environmental Monitoring and Assessment, 2011)

Quantitative estimation of the shrub canopy LAI from atmosphere-corrected HJ-1 CCD data in Mu Us Sandland - Wei Chen; ChunXiang Cao; QiSheng He; HuaDong Guo; Hao Zhang; RenQiang Li; Sheng Zheng; Min Xu; MengXu Gao; Jian Zhao; Sha Li; XiLiang Ni; et al. (Science China Earth Sciences, 2010)

Initial responses of soil CO2 efflux and C, N pools to experimental warming in two contrasting forest ecosystems, Eastern Tibetan Plateau, China - Zhenfeng Xu; Chuan Wan; Pei Xiong; Zheng Tang; Rong Hu; Gang Cao; Qing Liu (Plant and Soil, 2010)

Design, Recombinant Expression, and Antibacterial Activity of the Cecropins–Melittin Hybrid Antimicrobial Peptides - Yu Cao; Rong Qing Yu; Yi Liu; Huo Xiang Zhou; Ling Ling Song; Yi Cao; Dai Rong Qiao (Current Microbiology, 2010)

A preliminary study of the Six-Item Screener in detecting cognitive impairment - Mei-Rong Chen; Qi-Hao Guo; Xin-Yi Cao; Zhen Hong; Xiao-Hong Liu (Neuroscience Bulletin, 2010)

The complete mitogenome and phylogenetic analysis of Bombyx mandarina strain Qingzhou - Xiao-long Hu; Guang-li Cao; Ren-yu Xue; Xiao-jian Zheng; Xing Zhang; Hai-rong Duan; Cheng-liang Gong (Molecular Biology Reports, 2010)

The polymorphisms of UCP1 genes associated with fat metabolism, obesity and diabetes - Jun-jing Jia; Yun-bo Tian; Zhen-hui Cao; Lin-li Tao; Xi Zhang; Si-zhen Gao; Chang-rong Ge; Qiu-Ye Lin; M. Jois (Molecular Biology Reports, 2010)

Variation and Patterns of DNA Methylation in Maize C-type CMS Lines and their Maintainers - Yanli Lu; Yaxi Liu; Jing Wang; Moju Cao; Tingzhao Rong (Journal of Plant Biochemistry and Biotechnology, 2010)

Manganese-induced changes of the biochemical characteristics of the recombinant wild-type and mutant PrPs - Xiao-Li Li; Chen-Fang Dong; Gui-Rong Wang; Rui-Min Zhou; Qi Shi; Chan Tian; Chen Gao; Guo-Yong Mei; Cao Chen; Kun Xu; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2009)

Detection of survivin-expressing circulating cancer cells in the peripheral blood of patients with esophageal squamous cell carcinoma and its clinical significance - Mei Cao; Shang-Mian Yie; Sheng-Min Wu; Shu Chen; Be Lou; Xu He; Shang-Rong Ye; Ke Xie; Lin Rao; En Gao; Nai-Yao Ye (Clinical & Experimental Metastasis, 2009)

Effects of a Copper-Resistant Fungus on Copper Adsorption and Chemical Forms in Soils - Aixue Du; Lixiang Cao; Renduo Zhang; Rong Pan (Water, Air, & Soil Pollution, 2009)

Increased expression of Toll-like receptors 4 and 9 in human lung cancer - Yan-Bei Zhang; Feng-Lian He; Ming Fang; Tian-Feng Hua; Bi-Dan Hu; Zhi-Hong Zhang; Qi Cao; Rong-Yu Liu (Molecular Biology Reports, 2009)

Phase I clinical trial on intracoronary administration of Ad-hHGF treating severe coronary artery disease - Zhi-Jian Yang; You-Rong Zhang; Bo Chen; Shu-Lan Zhang; En-Zhi Jia; Lian-Sheng Wang; Tie-Bing Zhu; Chun-Jian Li; Hui Wang; Jun Huang; Ke-Jiang Cao; Wen-Zhu Ma; et al. (Molecular Biology Reports, 2009)

No spatial memory deficit exists in Kunming mice that recently recovered from motor defects following 3-nitropropionic acid intoxication - Xiao-Min Li; Bing-Gen Zhu; Jian-Bo Ni; Chun-Yan Cao; Jie-Ping Zhang; Xu-Dong Zhao; Rong-Shen Zhu (Neuroscience Bulletin, 2009)

Hypertonic stimulation induces synthesis and release of glutamate in cultured rat hypothalamic astrocytes and C6 cells - Rong Cao; Shan Jiang; Li Duan; Ying-Fei Xiong; Bei Gao; Zhi-Ren Rao (Neuroscience Bulletin, 2008)

hBolA, novel non-classical secreted proteins, belonging to different BolA family with functional divergence - Yu-Bo Zhou; Jia-Bing Cao; Bing-Bing Wan; Xin-Rong Wang; Guo-Hui Ding; Hong Zhu; Hong-Meng Yang; Ke-Sheng Wang; Xin Zhang; Ze-Guang Han (Molecular and Cellular Biochemistry, 2008)

Cloning and expression study of a putative carotene biosynthesis related (cbr) gene from the halotolerant green alga Dunaliella salina - Chen Chen; Lin Han Bai; Dai Rong Qiao; Hui Xu; Gui Ling Dong; Kun Ruan; Fei Huang; Yi Cao (Molecular Biology Reports, 2008)

Cloning and sequence analysis of the gene encoding 19-kD subunit of Complex I from Dunaliella salina - Yi Liu; Dai Rong Qiao; Hong Bo Zheng; Xu Lan Dai; Lin Han Bai; Jing Zeng; Yi Cao (Molecular Biology Reports, 2008)

Settlement, growth and survival of abalone, Haliotis discus hannai, in response to eight monospecific benthic diatoms - Rong-lian Xing; Chang-hai Wang; Xue-bin Cao; Ya-qing Chang (Journal of Applied Phycology, 2008)

TNFα-initiated oxidative/nitrative stress mediates cardiomyocyte apoptosis in traumatic animals - Shuzhuang Li; Ling Tao; Xiangying Jiao; Huirong Liu; Yue Cao; Bernard Lopez; Rong-Hua Luan; Theodore Christopher; Xin L. Ma (Apoptosis, 2007)

Methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms and the risk of primary Hepatocellular Carcinoma (HCC) in a Chinese population - Li-Na Mu; Wei Cao; Zuo-Feng Zhang; Lin Cai; Qing-Wu Jiang; Nai-Chieh You; Binh Yang Goldstein; Guo-Rong Wei; Chuan-Wei Chen; Qing-Yi Lu; Xue-Fu Zhou; Bao-Guo Ding; et al. (Cancer Causes & Control, 2007)

Nematicidal Resorcylides from the Aquatic Fungus Caryospora callicarpa YMF1.01026 - Jinyan Dong; Yanhui Zhu; Hongchuan Song; Ru Li; Hongping He; Haiyang Liu; Rong Huang; Yongping Zhou; Le Wang; Yi Cao; Keqin Zhang (Journal of Chemical Ecology, 2007)

OsGLU1, A Putative Membrane-bound Endo-1,4-ß-D-glucanase from Rice, Affects Plant Internode Elongation - Hua-Lin Zhou; Si-Jie He; Yang-Rong Cao; Tao Chen; Bao-Xing Du; Cheng-Cai Chu; Jin-Song Zhang; Shou-Yi Chen (Plant Molecular Biology, 2006)

Effects of fibroblast-mediated interleukin 3 and interleukin 6 gene therapy on hematopoiesis in mice treated with 5-fluorouracil - X. Cao; Dian Wen Ju; Rong Cai; Q. Tao; Yizhi Yu; Jianli Wang (Journal of Molecular Medicine, 1998)